Resin prism for polarization beam splitter

The resin prism for polarization beam splitters addresses image blurriness by controlling phase difference, fluorescent content, and birefringence through a methacrylic resin composition, achieving clear and stable images in head-mounted displays.

CN113466971BActive Publication Date: 2024-12-13ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202010343389.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2020-04-27
Publication Date
2024-12-13
Estimated Expiration
2040-04-27

AI Technical Summary

Technical Problem

Existing resin prisms for polarization beam splitters suffer from image blurriness due to the presence of fluorescent substances and birefringence, which are not adequately addressed by previous methods to reduce stress distortion during molding.

Method used

A resin prism with specific properties including an average phase difference of less than 10 nm, controlled fluorescent substance content, glass transition temperature between 120°C and 160°C, a photoelastic coefficient of 3.0×10^-12 Pa^-1, and a methacrylic resin composition with structural units like N-substituted maleimide and glutarimide, which reduces birefringence and maintains clarity.

Benefits of technology

The solution provides a clear and stable image with reduced birefringence, ensuring high extinction coefficients and effective light transmission, suitable for applications in head-mounted displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113466971B_ABST
    Figure CN113466971B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a resin prism that can obtain a clear image when used in a polarization beam splitter. The resin prism for a polarization beam splitter of the present invention is characterized in that the average value of the absolute value of the phase difference is less than 10 nm, and the content of the fluorescent light-emitting substance obtained by using the concentration-intensity conversion formula of the ethanol solution of fluorescein based on the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving in chloroform is measured at an excitation wavelength of 436 nm is 0.1×10 ‑9 ~4.0×10 ‑9 mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin prism for a polarization beam splitter. Background Art

[0002] A polarizing beam splitter (PBS) is a polarizing beam splitter that can split incident light into a P polarized light component and an S polarized light component, and is used in optical pickups, reflective liquid crystal projectors, etc. In recent years, various electronic technologies known as VR (Virtual Reality) and AR (Augmented Reality) have developed rapidly, and head-mounted display (HMD: Head Mounted Display) products have become popular as image display devices, and an optical system with a polarizing beam splitter configured in its image projection unit or image display unit has been proposed (Patent Documents 1 to 2).

[0003] On the other hand, a head-mounted display is an image display device worn on the head and used, so it is required to be small, lightweight, and less uncomfortable when worn. Therefore, in order to reduce the prism-shaped polarization beam splitter, a scheme of changing the previous glass prism to a resin has been proposed. Since the orientation and stress distortion generated during the molding process of the resin easily cause birefringence, a scheme of using the following resin prism is proposed, wherein the resin prism reduces the birefringence by using a prism forming method that is not easy to cause stress distortion or a resin material that is not easy to cause birefringence (Patent Documents 3 to 4).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-116409.

[0007] Patent document 2: Japanese Patent Application Publication No. 2015-161737.

[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-532729.

[0009] Patent document 4: Japanese Patent Application Publication No. 2018-156081. Summary of the invention

[0010] However, the present inventors have conducted studies and have found that, in a polarization beam splitter using a resin prism, a sufficiently clear image cannot be obtained simply by reducing the birefringence of the prism.

[0011] Therefore, an object of the present invention is to provide a resin prism for a polarization beam splitter that can obtain a clear image.

[0012] The present inventors conducted intensive research to solve the above-mentioned problems and found that, in a polarization beam splitter formed using a prism formed of a low-birefringence resin, the content of fluorescent substances accidentally contained in the prism affects the clarity of the image obtained through the polarization beam splitter, thereby completing the present invention.

[0013] That is, the present invention is as follows.

[0014] [1] A resin prism for a polarization beam splitter, characterized in that:

[0015] The average value of the absolute value of the phase difference is less than 10nm.

[0016] The content of the fluorescent substance was calculated from the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving in chloroform was measured at an excitation wavelength of 436 nm, and the concentration-intensity conversion formula of the ethanol solution of fluorescein was 0.1×10 -9 ~4.0×10 -9 mol / L.

[0017] [2] The resin prism for a polarization beam splitter according to [1], wherein the glass transition temperature Tg is higher than 120° C. and lower than 160° C.

[0018] [3] The resin prism for a polarization beam splitter according to [1] or [2], wherein the absolute value of the photoelastic coefficient is 3.0×10 -12 Pa -1 the following.

[0019] [4] The resin prism for a polarization beam splitter according to any one of [1] to [3], comprising a methacrylic resin.

[0020] [5] The resin prism for a polarization beam splitter according to [4], wherein the methacrylic resin includes a methacrylic resin having a structural unit X, and the structural unit X is a structural unit having a ring structure in a main chain.

[0021] [6] The resin prism for a polarization beam splitter according to [5], wherein the structural unit X contains at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide-based structural unit, and a lactone ring structural unit.

[0022] [7] The resin prism for a polarization beam splitter according to [5], wherein the structural unit X includes a structural unit derived from an N-substituted maleimide monomer.

[0023] [8] The resin prism for a polarization beam splitter according to [5], wherein the structural unit X includes a glutarimide-based structural unit.

[0024] According to the present invention, a resin prism for a polarization beam splitter capable of obtaining a clear image can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of an experimental system manufactured to evaluate the characteristics of a polarization beam splitter using the resin prism for a polarization beam splitter of the present invention in Examples.

[0026] The description of the accompanying drawings is as follows.

[0027] 1: blue LED; 2: collimating lens; 3: polarizing beam splitter; 4: reflective liquid crystal panel (LCOS); 5: projection lens; 6: screen; 31, 32: resin prisms; 33: reflective polarizing film. DETAILED DESCRIPTION

[0028] Hereinafter, this specific embodiment (hereinafter referred to as “this embodiment”) will be described in detail, but the present invention is not limited to the following description and can be implemented with various modifications within the scope of the gist.

[0029] [Resin prism for polarization beam splitter]

[0030] The resin prism for polarization beam splitter of the present embodiment is characterized in that the average value of the absolute value of the phase difference of the prism is less than 10 nm, and the content of the fluorescent substance obtained by using the concentration-intensity conversion formula of the ethanol solution of fluorescein based on the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving in chloroform is measured at an excitation wavelength of 436 nm is 0.1×10 -9 ~4.0×10 -9 mol / L.

[0031] -Prism Phase Difference-

[0032] Regarding the resin prism for the polarization beam splitter in this embodiment, the average value of the absolute value of the phase difference of the prism is less than 10nm, preferably less than 8nm, and more preferably less than 6nm. The average value of the absolute value of the phase difference is less than 10nm, thereby obtaining a polarization beam splitter with a high extinction coefficient and providing a clear image.

[0033] Here, the phase difference of the prism is a value measured by an optical path length equal to the optical path length of the transmitted light in the prism when the prism is made into a polarization beam splitter, and specifically, it can be measured by the method described in the embodiment described later.

[0034] -Content of fluorescent substances-

[0035] Regarding the resin prism for polarization beam splitter in the present embodiment, the content of the fluorescent substance obtained by using the concentration-intensity conversion formula of the ethanol solution of fluorescein is 0.1×10 -9 ~4.0×10 - 9 mol / L, preferably 0.2×10 -9 ~3.5×10 -9 mol / L, more preferably 0.3×10 -9 ~3.0×10 -9 mol / L, more preferably 0.3×10 -9 ~2.5×10 -9 mol / L. When the content of the fluorescent substance is below the upper limit, an image with high color reproduction can be obtained, and the image can be clearly distinguished without blurring. In addition, when the content of the fluorescent substance is above the lower limit, it is possible to suppress the low-wavelength light that is harmful to the naked eye from entering the naked eye more than necessary.

[0036] The reason why the image appears blurry when the fluorescence intensity is high (the content of fluorescent material is high) is not clear, but it is presumed that when fluorescence is generated by light passing through the prism, the light also goes in a direction other than the original direction of the transmitted light, resulting in a blurry image.

[0037] It should be noted that, when a hard coating or an anti-reflection coating is applied on the surface of the resin prism, the content of the fluorescent substance is measured after removing the coating. Specifically, it can be measured by the method described in the examples described later.

[0038] -Glass transition temperature-

[0039] The glass transition temperature (Tg) of the resin prism for polarization beam splitter in the present embodiment is preferably higher than 120°C and lower than 160°C.

[0040] From the viewpoint of heat resistance against heat generated by display devices such as head-mounted displays and the occurrence of photoelastic birefringence associated with dimensional changes, the glass transition temperature of the resin prism for the polarization beam splitter is preferably greater than 120° C. From the viewpoint of dimensional stability at the ambient temperature of use, the glass transition temperature (Tg) is more preferably 125° C. or higher, and further preferably 130° C. or higher.

[0041] On the other hand, when the glass transition temperature (Tg) is 160°C or less, melt processing at extremely high temperatures can be avoided, thermal decomposition of resins etc. can be suppressed, and good products can be obtained. From the viewpoint of obtaining the above-mentioned effects, the glass transition temperature (Tg) is preferably 150°C or less, and more preferably 140°C or less.

[0042] The glass transition temperature (Tg) can be determined by measuring in accordance with JIS-K7121. Specifically, it can be determined by the method described in the examples described below.

[0043] -Photoelastic coefficient C R -

[0044] The photoelastic coefficient C of the resin prism for the polarization beam splitter of this embodiment is R The absolute value of |C R |, preferably 3.0×10 -12 Pa -1 Below, more preferably 2.0×10 -12 Pa -1 Below, more preferably 1.5×10 -12 Pa -1 Below, more preferably 1.0×10 -12 Pa -1 The photoelastic coefficient is described in various documents (for example, see "General Theory of Chemistry", No. 39, 1998 (published by the Society Publishing Center)), and is defined by the following formulas (ia) and (ib). It can be seen that the photoelastic coefficient C R The closer the value of is to zero, the smaller the change in birefringence due to external forces.

[0045] |C R |=|Δn| / σ R (ia)

[0046] |Δn|=|nx-ny|(ib)

[0047] (In the formula, C R represents the photoelastic coefficient, σ R represents tensile stress, |Δn| represents the absolute value of birefringence, nx represents the refractive index in the stretching direction, and ny represents the refractive index in the direction perpendicular to the stretching direction in the plane.

[0048] As long as the photoelastic coefficient C of the resin prism of this embodiment is R The absolute value of |C R |3.0×10 -12 Pa -1As a result, it is possible to obtain a resin prism in which stress generated when the prism is fixed and photoelastic birefringence generated due to dimensional temperature change are sufficiently small, and a clear image can be obtained.

[0049] It should be noted that the photoelastic coefficient C R The determination is performed by cutting the resin prism into thin pieces and then using a vacuum compression molding machine to form a pressed film. In the case where a hard coating or an anti-reflection coating is applied on the surface of the resin prism, the coating is removed and then the determination is performed. Specifically, the determination is performed by the method described in the examples below.

[0050] -Light transmittance-

[0051] Regarding the resin prism for polarizing beam splitter of the present embodiment, the transmittance in the thickest part measured by using a spectrophotometer with a D65 light source and a 10° field of view, the ratio (T450 / T680) of the transmittance at a wavelength of 450 nm (T450) to the transmittance at a wavelength of 680 nm (T680) is preferably 0.95 to 1.03, more preferably 0.97 to 1.01, and even more preferably 0.98 to 1.00. When the ratio (T450 / T680) is within the above range, an image with good color tone can be obtained.

[0052] It should be noted that the light transmittance can be specifically measured by the method described in the Examples below.

[0053] -Molecular weight and molecular weight distribution-

[0054] The weight average molecular weight (Mw) of the resin prism for polarization beam splitter in the present embodiment, measured by gel permeation chromatography (GPC) in terms of polymethyl methacrylate, is preferably in the range of 80,000 to 170,000, more preferably in the range of 100,000 to 160,000, even more preferably in the range of 100,000 to 150,000, and even more preferably in the range of 120,000 to 150,000. If the weight average molecular weight (Mw) is in the above range, the balance between mechanical strength and fluidity is also excellent.

[0055] The weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) of the resin prism can be measured using the following apparatus and conditions.

[0056] · Measurement apparatus: Gel permeation chromatograph (HLC-8320GPC) manufactured by Tosoh Corporation.

[0057] ·The measurement conditions are as follows.

[0058] Chromatographic columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-Ms, and one TSKgel SuperH2500 were connected in series.

[0059] Column temperature: 40°C.

[0060] The developing solvent was tetrahydrofuran, and the flow rate was 0.6 mL / min. As an internal standard, 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added.

[0061] Detector: RI (differential refractometer) detector.

[0062] Detection sensitivity: 3.0mV / min.

[0063] Sample: 0.02 g of a resin prism in 20 mL of tetrahydrofuran.

[0064] Injection volume: 10 μL.

[0065] Standard samples for calibration curves: The following ten types of polymethyl methacrylates having known monodisperse weight peak molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0066] Weight peak molecular weight (Mp)

[0067] Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850

[0068] Under the above-mentioned conditions, the RI detection intensity with respect to the elution time of the resin prism was measured.

[0069] In the above, based on each calibration curve obtained by measuring the calibration curve standard sample, the weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) of the resin prism are obtained, and the molecular weight distribution (Mw / Mn) and (Mz / Mw) are determined using these values. It should be noted that when a hard coating or an anti-reflection coating is applied on the surface of the resin prism, the measurement is performed after removing these coatings.

[0070] -Methanol insoluble components-

[0071] The amount of the methanol-insoluble component of the resin prism for the polarization beam splitter in this embodiment is preferably 95% by mass or more, more preferably 95.5% by mass or more, more preferably 96% by mass or more, further preferably 96.5% by mass or more, particularly preferably 97% by mass or more, and most preferably 97.5% by mass or more, relative to the total amount of 100% by mass of the amount of the methanol-insoluble component and the amount of the methanol-soluble component. By setting the ratio of the amount of the methanol-insoluble component to 95% by mass or more, it is possible to suppress the troubles during molding such as the occurrence of silver streaks during injection molding.

[0072] It should be noted that the methanol-insoluble component and the methanol-soluble component refer to components obtained by dissolving a polarization beam splitter resin prism in chloroform to prepare a chloroform solution, then dropping the solution into a large excess of methanol to perform reprecipitation, separating the filtrate and the filter residue, and then drying each. When a hard coating or an anti-reflection coating is applied on the surface of the resin prism, the measurement is performed after removing these coatings.

[0073] Specifically, it can be obtained as follows. After dissolving 5g of resin prism in 100mL of chloroform, the solution is added to a dropping funnel and added dropwise to 1L of methanol stirred with a stirrer for about 1 hour to reprecipitate. After dropping all the amounts, let stand for 1 hour, then use a membrane filter (manufactured by Adbandek Toyo Co., Ltd., T050A090C) as a filter for suction filtration. The filter residue is vacuum dried at 60°C for 16 hours as a methanol-insoluble component. In addition, with respect to the filtrate, the bath temperature of the rotary evaporator is set to 40°C, the vacuum degree is gradually reduced from the initial setting of 390Torr to 30Torr at the end, and after removing the solvent, the soluble component remaining in the eggplant-shaped flask is recovered as a methanol-soluble component. The weight of the methanol-insoluble component and the weight of the methanol-soluble component were weighed, and the ratio (mass %) of the amount of the methanol-soluble component to the total amount (100 mass %) of the amount of the methanol-soluble component and the amount of the methanol-insoluble component (methanol-soluble component ratio) was calculated.

[0074] [Resin composition]

[0075] The resin prism for polarization beam splitter according to the present embodiment is preferably composed of a resin composition containing a methacrylic resin.

[0076] [Methacrylic resin]

[0077] The methacrylic resin included in the resin prism for polarization beam splitter of the present embodiment preferably includes a methacrylic resin having a structural unit X having a ring structure in the main chain and a structural unit derived from a methacrylate monomer. By including a methacrylic resin, particularly a methacrylic resin including a structural unit X having a ring structure in the main chain and a methacrylate monomer unit, a resin prism having a sufficiently small phase difference and a sufficiently small photoelastic coefficient can be obtained.

[0078] Hereinafter, each structural unit will be described.

[0079] -Structural unit derived from methacrylate monomer-

[0080] As the structural unit derived from the methacrylic acid ester monomer, for example, there can be mentioned a structural unit derived from a monomer selected from the methacrylic acid esters shown below. As the methacrylic acid ester, for example, there can be mentioned methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, 2,4,6-tribromophenyl methacrylate, and the like.

[0081] These monomers may be used alone or in combination of two or more.

[0082] As the structural unit derived from the methacrylate monomer, a structural unit derived from methyl methacrylate and benzyl methacrylate is preferred because the resulting methacrylic resin has excellent transparency and weather resistance.

[0083] The structural unit derived from the methacrylate monomer may be contained in one kind or in two or more kinds.

[0084] The resin prism for polarization beam splitter of this embodiment can reduce the birefringence caused by orientation and residual stress during molding by appropriately adjusting the ratio of the structural unit X having a ring structure on the main chain to the structural unit derived from the methacrylate monomer, and can obtain a resin prism with an average value of the absolute value of the phase difference of less than 10nm. In addition, by appropriately adjusting the above ratio, the methacrylic resin can be fully given heat resistance. From these viewpoints, the content of the structural unit derived from the methacrylate monomer is preferably 50 to 97% by mass, more preferably 55 to 97% by mass, further preferably 55 to 95% by mass, further more preferably 60 to 93% by mass, and particularly preferably 60 to 90% by mass, based on 100% by mass of the methacrylic resin.

[0085] It should be noted that the content of the structural unit derived from the methacrylate monomer can be determined by 1 H-NMR determination and 13 For example, CDCl can be used as a measuring solvent. 3 or DMSO-d 6 , measured at 40°C 1 H-NMR determination and 13 C-NMR determination.

[0086] The structural unit X having a ring structure in the main chain will be described below.

[0087] The structural unit X having a ring structure on the main chain preferably comprises at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide-based structural units, and lactone ring structural units, and more preferably consists of only at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide-based structural units, and lactone ring structural units. The structural unit X having a ring structure on the main chain may be one type or a combination of plural types or more.

[0088] -Structural unit derived from N-substituted maleimide monomer-

[0089] Next, the structural unit derived from the N-substituted maleimide monomer will be described.

[0090] The structural unit derived from the N-substituted maleimide monomer may be at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), and preferably, is formed of two structural units of the structural units represented by the following formula (1) and the following formula (2).

[0091] [Chemical formula 1]

[0092]

[0093] In formula (1), R 1 represents any one of an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms, and R 2 and R 3 Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0094] In addition, in R 2 or R 3 In the case of an aryl group, R 2 or R 3 A halogen atom may be contained as a substituent.

[0095] In addition, R 1 It may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group.

[0096] [Chemical formula 2]

[0097]

[0098] In formula (2), R 4 represents any one of a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, and an alkyl group having 1 to 12 carbon atoms, and R 5 and R 6 Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0099] A specific example is shown below.

[0100] Examples of the monomer (N-aryl maleimide, N-aromatic substituted maleimide, etc.) forming the structural unit represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthrylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, etc.

[0101] Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred because the resulting methacrylic resin has excellent optical properties such as heat resistance and birefringence.

[0102] These monomers may be used alone or in combination of two or more.

[0103] Examples of the monomer forming the structural unit represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, N-sec-butylmaleimide, N-tert-butylmaleimide, N-n-pentylmaleimide, N-n-hexylmaleimide, N-n-heptylmaleimide, N-octylmaleimide, N-laurylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, and the like.

[0104] Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred from the perspective of excellent weather resistance of methacrylic resins, and N-cyclohexylmaleimide is particularly preferred from the perspective of excellent low hygroscopicity required for optical materials in recent years.

[0105] These monomers may be used alone or in combination of two or more.

[0106] In the methacrylic resin of the present embodiment, it is particularly preferred to use the structural unit represented by the formula (1) and the structural unit represented by the formula (2) in combination, because highly controlled birefringence characteristics can be expressed.

[0107] The molar ratio (X1 / X2) of the content (X1) of the structural unit represented by formula (1) to the content (X2) of the structural unit represented by formula (2) is preferably greater than 0 and 15 or less, and more preferably greater than 0 and 10 or less.

[0108] When the molar ratio (X1 / X2) is within this range, the resin prism of the present embodiment maintains transparency without yellowing and exhibits good heat resistance and good photoelastic properties without impairing environmental resistance.

[0109] The content of the structural unit derived from the N-substituted maleimide monomer is preferably in the range of 5 to 40% by mass, more preferably in the range of 5 to 35% by mass, based on 100% by mass of the methacrylic resin.

[0110] When the content is within this range, the methacrylic resin can obtain a more sufficient improvement effect on heat resistance, and can obtain a more preferable improvement effect on weather resistance, low water absorption, and optical properties. It should be noted that in order to prevent the physical properties of the methacrylic resin from being reduced due to the reduction in the reactivity of the monomer components and the increase in the amount of unreacted and residual monomers during the polymerization reaction, it is effective to set the content of the structural unit derived from the N-substituted maleimide monomer to 40% by mass or less.

[0111] In addition, by appropriately adjusting the content of the structural unit derived from the N-substituted maleimide monomer within this range, the birefringence caused by the orientation and residual stress during molding can be reduced, and a resin prism for a polarization beam splitter having an average value of the absolute value of the phase difference of 10 nm or less can be obtained. The most suitable content of the structural unit derived from the N-substituted maleimide monomer varies depending on the type of N-substituted maleimide. For example, when methyl methacrylate is used as the methacrylate monomer and N-phenylmaleimide and N-cyclohexylmaleimide are used as the N-substituted maleimide monomer, it is preferably adjusted within the range of 79 to 83% by mass of the structural unit derived from methyl methacrylate, 6 to 8% by mass of the structural unit derived from N-phenylmaleimide, and 11 to 13% by mass of the structural unit derived from N-cyclohexylmaleimide.

[0112] The methacrylic resin having a structural unit derived from an N-substituted maleimide monomer and constituting the resin prism for a polarization beam splitter of the present embodiment may contain a structural unit derived from other monomers copolymerizable with the methacrylate monomer and the N-substituted maleimide monomer, within the scope not impairing the purpose of the present invention.

[0113] For example, examples of the other copolymerizable monomers include aromatic vinyl groups; unsaturated nitriles; acrylic acid esters having a cyclohexyl group, a benzyl group, or an alkyl group having 1 to 18 carbon atoms; glycidyl compounds; unsaturated carboxylic acids; and the like.

[0114] Examples of the aromatic vinyl group include styrene, α-methylstyrene, and divinylbenzene.

[0115] Examples of the unsaturated nitrile include acrylonitrile, methacrylonitrile, and ethacrylonitrile.

[0116] Examples of the acrylic acid ester include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, and butyl acrylate.

[0117] Examples of the glycidyl compound include glycidyl (meth)acrylate and the like.

[0118] Examples of the unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and half esters or anhydrides thereof.

[0119] The above-mentioned copolymerizable structural unit derived from other monomers may be present in one type or in two or more types.

[0120] The content of the structural unit derived from other copolymerizable monomers is preferably 0 to 10% by mass, more preferably 0 to 9% by mass, and even more preferably 0 to 8% by mass, based on 100% by mass of the methacrylic resin.

[0121] When the content of the structural unit derived from other monomers is within this range, the molding processability and mechanical properties of the resin can be improved without impairing the original effect of introducing the ring structure into the main chain, which is preferred.

[0122] It should be noted that the content of the structural unit derived from the N-substituted maleimide monomer and the content of the structural unit derived from other copolymerizable monomers can be calculated by 1 H-NMR determination and 13 For example, CDCl can be used as a measuring solvent. 3 or DMSO-d 6 , measured at 40°C 1 H-NMR determination and 13C-NMR determination.

[0123] -Glutarimide structural unit-

[0124] Examples of the methacrylic resin having a glutarimide structural unit in the main chain include methacrylic resins having a glutarimide structural unit described in JP-A-2006-249202, JP-A-2007-009182, JP-A-2007-009191, JP-A-2011-186482, and Japanese Re-examined Patent Publication No. 2012 / 114718. The methacrylic resins can be formed by the methods described in the publications.

[0125] The glutarimide structural unit constituting the methacrylic resin of the present embodiment can be formed after the resin is polymerized.

[0126] Specifically, the glutarimide structural unit can be a substance represented by the following general formula (3).

[0127] [Chemical formula 3]

[0128]

[0129] In the above general formula (3), preferably, R 7 and R 8 are independently a hydrogen atom or a methyl group, R 9 is any one of a hydrogen atom, a methyl group, a butyl group, and a cyclohexyl group, and more preferably, R 7 is methyl, R 8 is a hydrogen atom, R 9 It is methyl.

[0130] The glutarimide-based structural units may include a single type or a plurality of types.

[0131] In the methacrylic resin having a glutarimide structural unit, the content of the glutarimide structural unit is preferably in the range of 3 to 70 mass %, more preferably in the range of 3 to 60 mass %, based on 100 mass % of the methacrylic resin.

[0132] When the content of the glutarimide structural unit is within the above range, a resin having excellent molding processability, heat resistance, and optical properties can be obtained, which is preferred.

[0133] In addition, by appropriately adjusting the content of the glutarimide structural unit within this range, the birefringence caused by the orientation and residual stress during molding can be reduced, and a resin prism for a polarization beam splitter having an average value of the absolute value of the phase difference of 10 nm or less can be obtained. The most suitable content of the glutarimide structural unit depends on R of the general formula (3). 7 ~R 9 The type of substituents varies. For example, in R 7 and R 8 is a hydrogen atom, R 9 In the case of a methyl group, when the content of the glutarimide structural unit is in the range of 3 to 10 mass %, birefringence caused by orientation and residual stress during molding is reduced, and a resin prism for a polarization beam splitter having an average value of the absolute value of the phase difference of 10 nm or less can be obtained.

[0134] It should be noted that the content of the glutarimide structural unit in the methacrylic resin can be determined using the method described in the aforementioned patent document.

[0135] The methacrylic resin having a glutarimide structural unit may further contain an aromatic vinyl monomer unit as necessary.

[0136] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene and α-methylstyrene, and styrene is preferred.

[0137] The content of the aromatic vinyl unit in the methacrylic resin having a glutarimide structural unit is not particularly limited, but is preferably 0 to 20% by mass based on 100% by mass of the methacrylic resin having a glutarimide structural unit.

[0138] When the content of the aromatic vinyl unit is within the above range, both heat resistance and excellent photoelastic properties can be achieved, which is preferred.

[0139] For example, in the case of obtaining a resin by glutarimidizing a methyl methacrylate-styrene copolymer obtained by copolymerizing methyl methacrylate as a methacrylate monomer and styrene as an aromatic vinyl monomer, by adjusting the content of structural units derived from methyl methacrylate to 65 to 90% by mass, structural units derived from styrene to 5 to 15% by mass, and glutarimide-based structural units to 5 to 20% by mass, the birefringence caused by orientation and residual stress during molding can be reduced, and a resin prism for a polarization beam splitter having an average value of the absolute value of the phase difference of less than 10 nm can be obtained.

[0140] -Lactone ring structural unit-

[0141] The methacrylic resin having a lactone ring structural unit in the main chain can be formed by the methods described in, for example, JP-A-2001-151814, JP-A-2004-168882, JP-A-2005-146084, JP-A-2006-96960, JP-A-2006-171464, JP-A-2007-63541, JP-A-2007-297620, JP-A-2010-180305, and the like.

[0142] The lactone ring structural unit constituting the methacrylic resin of the present embodiment can be formed after polymerizing the resin.

[0143] The lactone ring structural unit in the present embodiment is preferably a six-membered ring from the viewpoint of excellent stability of the ring structure.

[0144] As the six-membered lactone ring structural unit, for example, a structure represented by the following general formula (4) is particularly preferred.

[0145] [Chemical formula 4]

[0146]

[0147] In the above general formula (4), R 10 , R 11 and R 12 They are independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms.

[0148] As organic residues, for example, there can be mentioned saturated aliphatic hydrocarbon groups (alkyl groups, etc.) having 1 to 20 carbon atoms, such as methyl, ethyl, propyl, etc.; unsaturated aliphatic hydrocarbon groups (alkenyl groups, etc.) having 2 to 20 carbon atoms, such as vinyl, propenyl, etc.; aromatic hydrocarbon groups (aryl groups, etc.) having 6 to 20 carbon atoms, such as phenyl, naphthyl, etc.; groups in which one or more hydrogen atoms in these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups are substituted with at least one group selected from the group consisting of hydroxyl groups, carboxyl groups, ether groups, and ester groups; etc.

[0149] For example, after a hydroxyl group and an ester group or a carboxyl group are introduced into the molecular chain by copolymerizing an acrylic monomer having a hydroxyl group with a methacrylate monomer such as methyl methacrylate, dealcoholization (esterification) or dehydration condensation (hereinafter also referred to as "cyclization condensation reaction") occurs between these hydroxyl groups and the ester group or the carboxyl group, thereby forming a lactone ring structural unit.

[0150] Examples of acrylic monomers having a hydroxyl group used in the polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, 2-(hydroxymethyl)acrylic acid alkyl esters (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, tert-butyl 2-(hydroxymethyl)acrylate), and 2-(hydroxyethyl)acrylic acid alkyl esters. Preferred are monomers having a hydroxyalkyl moiety, i.e., 2-(hydroxymethyl)acrylic acid and 2-(hydroxymethyl)acrylic acid alkyl esters, and particularly preferred are methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate.

[0151] The content of the lactone ring structural unit in the methacrylic resin having a lactone ring structural unit in the main chain is preferably 5 to 40% by mass, more preferably 5 to 35% by mass, based on 100% by mass of the methacrylic resin.

[0152] When the content of the lactone ring structural unit is within this range, the ring structure introduction effect such as improved solvent resistance and improved surface hardness can be exhibited while maintaining molding processability. In addition, by appropriately adjusting the content of the lactone ring structural unit within this range, the birefringence caused by the orientation and residual stress during molding is reduced, and a resin prism for a polarization beam splitter having an average value of the absolute value of the phase difference of 10 nm or less can be obtained.

[0153] It should be noted that the content of the lactone ring structure in the methacrylic resin can be determined using the method described in the aforementioned patent document.

[0154] The methacrylic resin having a lactone ring structural unit in the main chain may have a structural unit derived from other monomers copolymerizable with the above-mentioned methacrylate monomer and the acrylic monomer having a hydroxyl group.

[0155] Examples of such other copolymerizable monomers include monomers having polymerizable double bonds such as styrene, vinyltoluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, methylallyl alcohol, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, and N-vinyl carbazole.

[0156] These other monomers (constituent units) may be present in one kind or in two or more kinds.

[0157] The content of the structural unit derived from the other copolymerizable monomer is preferably 0 to 20% by mass based on 100% by mass of the methacrylic resin, more preferably less than 10% by mass, and further preferably less than 7% by mass from the viewpoint of weather resistance.

[0158] The methacrylic resin in the present embodiment may have only one type of the structural unit derived from the above-mentioned other copolymerizable monomer, or may have two or more types of the structural unit derived from the above-mentioned other copolymerizable monomer.

[0159] The methacrylic resin in the present embodiment preferably has at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide structural unit, and a lactone ring structural unit. Among them, it is particularly preferred to have a structural unit derived from an N-substituted maleimide monomer from the viewpoint of being easy to highly control optical properties such as a photoelastic coefficient without mixing with other thermoplastic resins. In addition, it is particularly preferred to have a glutarimide structural unit from the viewpoint of obtaining a high-strength resin-made prism.

[0160] [Method for producing methacrylic resin]

[0161] Hereinafter, the method for producing the methacrylic resin according to the present embodiment will be described.

[0162] -Method for producing methacrylic resin containing structural units derived from N-substituted maleimide monomer-

[0163] As a method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer in the main chain (hereinafter sometimes referred to as a "maleimide copolymer"), any polymerization method of bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, and emulsion polymerization can be cited. From the viewpoint of being able to reduce the amount of residual monomers and impurities contained in the resin prism, suspension polymerization, bulk polymerization, and solution polymerization are preferred, and solution polymerization is more preferred.

[0164] In the production method of the present embodiment, as a polymerization method, for example, any of a batch polymerization method, a semi-batch method, and a continuous polymerization method can be used.

[0165] In this embodiment, from the viewpoint of being able to reduce the amount of residual maleimide at the time of polymerization termination and reduce the fluorescence intensity (reduce the content of fluorescent light-emitting substances), it is preferred to use the so-called semi-batch polymerization method, which is a method in which a part of the monomer is loaded into the reactor before the start of polymerization, the polymerization is started by adding a polymerization initiator, and then the remaining part of the monomer is supplied.

[0166] In a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, as a method for controlling the obtained resin prism to show a predetermined fluorescence intensity (the content of the fluorescent light-emitting substance is within a predetermined range), at least one method selected from (1) to (3) can be cited: (1) using an N-substituted maleimide monomer with a controlled content of specific impurities as a raw material; (2) applying a polymerization method to reduce the amount of unreacted N-substituted maleimide remaining after the polymerization is completed; (3) applying a devolatilization method to reduce shear. Among them, it is preferred to select a production method combining (1) and (3) or a production method combining all three.

[0167] (1) Control of impurities in N-substituted maleimide

[0168] As one of the impurities in N-substituted maleimide that provides fluorescence to methacrylic resin, 2-amino-N-substituted succinimide produced by the reaction of N-substituted maleimide with primary amine can be cited. As 2-amino-N-substituted succinimide, 2-cyclohexylamino-N-cyclohexylsuccinimide, 2-anilino-N-phenylsuccinimide, etc. can be cited. 2-amino-N-substituted succinimide not only has fluorescence itself, but also, through the research of the inventors, it has been clarified that although the detailed modification mechanism is unclear, if it is heated at 300°C or above or supplied to a devolatilization device with shearing, a thermally modified product with fluorescence is generated. That is, in order to control the fluorescence intensity of methacrylic resin and the obtained resin prism, it is preferred to reduce the 2-amino-N-substituted succinimide contained in N-substituted maleimide and use a devolatilization device without a rotating part in the production of methacrylic resin and perform devolatilization at 300°C or below.

[0169] Examples of a method for controlling impurities in the N-substituted maleimide include providing a pretreatment step of washing the N-substituted maleimide with water (water washing step) and / or dehydrating the N-substituted maleimide (dehydration step).

[0170] The above-mentioned pretreatment step may be water washing alone or a combination of water washing and dehydration. In addition, water washing and dehydration may be performed once or twice or more. In the above-mentioned pretreatment step, a concentration adjustment step may be further provided for adjusting the concentration of the N-substituted maleimide solution obtained in the dehydration step.

[0171] In this embodiment, for example, 2-amino-N-substituted succinimide in N-substituted maleimide is removed by a water washing step shown below, and then water is removed in a dehydration step, thereby obtaining an N-substituted maleimide solution, which is suitable for preparing a methacrylic resin with controlled fluorescence intensity and good color tone.

[0172] In the water washing step, for example, the following method can be used: N-substituted maleimide is dissolved in a water-insoluble organic solvent, separated into an organic layer and an aqueous layer, the organic layer is mixed and washed with one or more liquids selected from an acidic aqueous solution, water, and an alkaline aqueous solution in batches, continuously, or both, and then the organic layer and the aqueous layer are separated.

[0173] When the amount of N-substituted maleimide in the organic layer is set to 100% by mass, the amount of 2-amino-N-substituted succinimide in the organic layer after the water washing process is preferably less than 5 mass ppm, more preferably more than 0.1 mass ppm and less than 1 mass ppm. When the amount of 2-amino-N-substituted succinimide in the organic layer is within this range, the concentration of the fluorescent light-emitting substance in the methacrylic resin and the obtained resin prism can be controlled within the above range, and a resin prism for a polarization beam splitter that can obtain a clear image can be obtained, so it is preferred. In addition, it is also preferred from the cost aspect in cleaning. In the case where a dehydration process is not provided, the organic layer containing N-substituted maleimide obtained in the water washing process can be used as an N-substituted maleimide solution in the polymerization process.

[0174] The amount of 2-amino-N-substituted succinimide in the organic layer can be measured, for example, by using isopropyl benzoate as an internal standard substance with a gas chromatograph, a liquid chromatograph, or the like. Specifically, it can be measured by the method described in the Examples described below.

[0175] The water-insoluble organic solvent used is not particularly limited as long as it is a solvent that dissolves N-substituted maleimide and 2-amino-N-substituted succinimide, phase-separates with water, and has an azeotropic point with water. Specifically, for example, aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as chloroform and dichloroethane; etc. can be used.

[0176] The water used may be sewage, pure water, or tap water.

[0177] In addition, the acidity of the acidic aqueous solution or the alkaline aqueous solution is not particularly limited.

[0178] The concentration of the N-substituted maleimide in the organic layer before the water washing step is preferably 0.5 mass % to 30 mass %, more preferably 10 mass % to 25 mass %, and even more preferably 20 mass % to 25 mass %.

[0179] The temperature when the organic layer and the aqueous layer are mixed and washed may be 40°C or higher, preferably 40°C or higher and 80°C or lower, and more preferably 50°C or higher and 60°C or lower.

[0180] When the mass of the organic layer is set to 100 mass%, the mass ratio of the water layer to the organic layer is preferably 5 mass% to 300 mass%, more preferably 10 mass% to 200 mass%, and further preferably 30 mass% to 100 mass%.

[0181] When the concentration of N-substituted maleimide in the organic layer, the liquid temperature during washing, and the mass ratio of the aqueous layer are within these ranges, the reaction between N-substituted maleimide and water is difficult to proceed, and 2-amino-N-substituted succinimide is easily extracted to the aqueous layer side, which is preferred.

[0182] When cleaning is performed in batches, the reaction tank used can be any of stainless steel and glass-lined, and reaction tanks other than these can also be used. In addition, there is no particular restriction on the shape of the stirring blade. As specific stirring blades, for example, three swept blades, four paddle blades, four inclined paddle blades, six turbine blades, and anchor blades can be used. In addition, Twin Star (ツインスター) and Full Zone (フルゾーン) made by Kobelco Environmental Solutions Co., Ltd. can also be used.

[0183] The stirring time is preferably more than 10 minutes and less than 120 minutes, more preferably more than 30 minutes and less than 60 minutes. In addition, about stirring speed, appropriately select the speed that mixed solution becomes turbulent state and does not emulsify. When stirring time, stirring speed are respectively in this range, stirring efficiency and the extraction efficiency of 2-amino-N-substituted succinimide in the water layer can be improved, and the 2-amino-N-substituted succinimide in N-substituted maleimide can be further reduced, so it is preferred.

[0184] When washing is performed continuously, an empty tower, a packed tower, or a plate tower may be used. A static mixer such as a static mixer or a rotary mixer such as a dynamic mixer may be used.

[0185] The contact time between the organic layer and the aqueous layer is preferably set to be between 1 second and 60 minutes, more preferably between 30 seconds and 10 minutes. When the contact time is within this range, the reaction between the N-substituted maleimide and water is difficult to proceed, and the 2-amino-N-substituted succinimide is easily extracted to the aqueous layer side, so it is preferred.

[0186] In the dehydration step, the organic layer is supplied to a reaction tank and heated under reduced pressure to remove water. The pressure and temperature are not particularly limited as long as the solvent used forms an azeotropic composition with water.

[0187] The water content in the organic layer after the dehydration step is preferably 100 mass ppm or less when the mass of the organic layer is 100 mass %. When the water content after the dehydration step is within this range, the deterioration of the color tone caused by water during the polymerization of the methacrylic resin can be suppressed, and the amount of the solvent distilled off together with the water can be reduced, which is also preferred from the perspective of cost.

[0188] The organic layer containing N-substituted maleimide obtained in the dehydration step may be used as an N-substituted maleimide solution in the polymerization step, or the N-substituted maleimide solution whose concentration has been adjusted in the concentration adjustment step may be used in the polymerization step.

[0189] In the concentration adjustment step, for example, the organic layer of the N-substituted maleimide obtained in the dehydration step can be diluted with the water-insoluble organic solvent. The water-insoluble organic solvent used in the concentration adjustment step is preferably the same as the water-insoluble organic solvent used in the water washing step.

[0190] The N-substituted maleimide solution obtained in the above-mentioned pretreatment step is preferably a solution (organic layer) of the above-mentioned water-insoluble organic solvent.

[0191] In the N-substituted maleimide solution obtained by the above-mentioned pretreatment step, the mass ratio of 2-amino-N-substituted succinimide contained in the above-mentioned N-substituted maleimide solution relative to 100 mass % of the N-substituted maleimide contained in the above-mentioned N-substituted maleimide solution is preferably 5 mass ppm or less, and more preferably 0.1 mass ppm or more and 1 mass ppm or less.

[0192] The water content in the N-substituted maleimide solution obtained in the pretreatment step is preferably 200 mass ppm or less, more preferably 100 to 200 mass ppm, based on 100 mass ppm of the N-substituted maleimide solution.

[0193] The mass ratio of the N-substituted maleimide contained in the N-substituted maleimide solution obtained by the above-mentioned pretreatment step is preferably 5 to 30 mass %, and more preferably 5 to 25 mass %, relative to 100 mass % of the N-substituted maleimide solution. In the case of this range, the N-substituted maleimide is difficult to precipitate and can be transported in a uniform solution, so it is preferred.

[0194] When a plurality of N-substituted maleimide solutions are used in the polymerization step, it is preferred that a mixed solution of the plurality of N-substituted maleimide solutions satisfies the mass ratio of the above-mentioned 2-amino-N-substituted succinimide, the above-mentioned water content and / or the mass ratio of the above-mentioned N-substituted maleimide, and it is more preferred that each N-substituted maleimide solution satisfies the mass ratio of the above-mentioned 2-amino-N-substituted succinimide, the above-mentioned water content and / or the mass ratio of the above-mentioned N-substituted maleimide.

[0195] By adopting the water washing step and dehydration step of the N-substituted maleimide as described above, the 2-amino-N-substituted succinimide having fluorescent light emission can be reduced, and the moisture that causes the deterioration of the color tone of the methacrylic resin can be removed, so that a methacrylic resin and a composition of the resin having good color tone even in a prism with a long optical path length can be obtained, which is preferred.

[0196] In the polymerization step, the methacrylate monomer, any other monomers, a polymerization initiator, a polymerization solvent, a chain transfer agent, etc. are mixed with the N-substituted maleimide solution obtained in the pretreatment step to prepare a monomer mixed solution, which is then used in the polymerization.

[0197] (2) Reduction of unreacted N-substituted maleimide at the end of polymerization

[0198] The present inventors have found that, although the detailed mechanism is unclear, if unreacted N-substituted maleimide is present at the end of polymerization of a methacrylic resin, a low molecular weight fluorescent reaction byproduct containing N-substituted maleimide as a structural unit is generated in a heated devolatilizer or the like.

[0199] In order to control the content of fluorescent light-emitting substances in the methacrylic resin and the obtained resin prism within the above-mentioned range, the total mass of unreacted N-substituted maleimide remaining after the polymerization is preferably 1000 mass ppm or less, more preferably 10 mass ppm or more and 500 mass ppm or less, relative to 100 mass % of the polymerization solution at the end of the polymerization.

[0200] In addition, when N-aryl maleimides such as N-phenylmaleimide are used as the N-substituted maleimide, the total mass of the unreacted N-aryl maleimide remaining after the completion of the polymerization is preferably 500 mass ppm or less, more preferably 10 mass ppm or more and 500 mass ppm or less, and further preferably 10 mass ppm or more and 50 mass ppm or less, relative to 100 mass ppm of the polymerization solution at the end of the polymerization.

[0201] When the content of the fluorescent substance in the methacrylic resin and the obtained resin prism is within these ranges, it is preferable. In addition, in order to set the amount of unreacted N-substituted maleimide to less than 10 mass ppm, it is necessary to increase the polymerization temperature or increase the amount of the polymerization initiator, so that the thermally modified maleimide and active free radicals increase, which causes the color tone of the methacrylic resin to deteriorate, so it is not preferable.

[0202] As a means of controlling the amount of unreacted N-substituted maleimide after the completion of the polymerization to the above-mentioned range, a semi-batch polymerization method can be cited. In the semi-batch polymerization method, it is preferred that in the polymerization process, from the beginning of the addition of the polymerization initiator to 30 minutes later, 5 to 35% by mass of methacrylate monomer is added based on the total mass of all monomers (e.g., methacrylate, N-substituted maleimide and any other monomers) supplied to the polymerization as 100% by mass. In other words, it is preferred that 65 to 95% by mass of the total mass of all monomers supplied to the polymerization, 100% by mass, is loaded into the reactor before the addition of the polymerization initiator, and the remaining part of 5 to 35% by mass of methacrylate monomer is added from the beginning of the addition of the polymerization initiator to 30 minutes later. The amount of methacrylate monomer added is preferably 10 to 30% by mass based on the total mass of all monomers supplied to the polymerization as 100% by mass. When the amount of the additionally added methacrylate monomer is within the above range, the unreacted N-substituted maleimide reacts with the additionally added methacrylate monomer, and the amount of the unreacted N-substituted maleimide after the completion of the polymerization can be controlled within the above range, which is preferred.

[0203] The starting time of the supplementary addition of the monomer, the speed of the supplementary addition, etc., can be appropriately selected according to the polymerization conversion rate. In addition, in addition to the methacrylate monomer, a monomer mixture containing an N-substituted maleimide monomer and other monomers can be supplemented to the extent that the effect of the present invention is not hindered and the amount of unreacted N-substituted maleimide is not hindered.

[0204] By adopting the semi-batch polymerization method as described above, the amount of unreacted N-substituted maleimide monomer in the second half of the polymerization can be reduced, the generation of fluorescent light-emitting substances in the devolatilization process can be minimized, and a methacrylic resin and a composition of the resin having good color tone even in a prism with a long optical path length can be obtained, so it is preferred.

[0205] Hereinafter, as an example of a method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, a case of producing the methacrylic resin by semi-batch radical polymerization using a solution polymerization method will be specifically described.

[0206] In the semi-batch polymerization method, preferably, 5 to 35% by mass of the methacrylate monomer is added after 30 minutes from the start of the addition of the polymerization initiator, based on the total mass of all monomers (methacrylate, N-substituted maleimide and any other monomers) supplied to the polymerization being 100% by mass. In other words, preferably, 65 to 95% by mass of the total mass of all monomers supplied to the polymerization being 100% by mass is charged into the reactor before the start of the polymerization, and the remaining 5 to 35% by mass of the methacrylate monomer is added after 30 minutes from the start of the addition of the polymerization initiator.

[0207] The amount of the methacrylic acid ester monomer to be supplementally added is more preferably 10 to 30% by mass, based on 100% by mass of the total mass of all monomers supplied for polymerization.

[0208] The start timing of the supplementary addition of the monomer, the rate of the supplementary addition, etc. may be appropriately selected according to the polymerization conversion rate.

[0209] Furthermore, in addition to the methacrylate monomer, a monomer mixture containing the N-substituted maleimide monomer and other monomers may be added as long as the effects of the present invention are not impaired and the conversion rate of the N-substituted maleimide monomer is not hindered.

[0210] By adopting the semi-batch polymerization method as described above, the conversion rate of the N-substituted maleimide monomer in the second half of the polymerization can be increased, the content of the fluorescent substance can be reduced, and a resin and a composition of the resin having excellent transmittance of a prism with a long optical path length, easy control of the molecular weight distribution of the obtained polymer, and fluidity that is particularly suitable for injection molding can be obtained, so it is preferred.

[0211] The polymerization solvent used is not particularly limited as long as it is a solvent that appropriately maintains the viscosity of the reaction solution for the purpose of improving the solubility of the maleimide copolymer obtained by polymerization and preventing gelation.

[0212] Specific examples of the polymerization solvent include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and cumene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone.

[0213] These may be used alone or in combination of two or more.

[0214] Furthermore, an alcohol such as methanol, ethanol, or isopropanol may be used as a polymerization solvent insofar as the dissolution of the polymerization product during polymerization is not inhibited.

[0215] The amount of solvent during polymerization is not particularly limited as long as it is an amount that allows polymerization to proceed, does not cause precipitation of copolymers and monomers used during production, and can be easily removed. For example, when the total amount of the monomers to be matched is 100% by mass, it is preferably 10 to 200% by mass, more preferably 25 to 150% by mass, further preferably 40 to 100% by mass, and further more preferably 50 to 100% by mass.

[0216] In the present embodiment, it is also preferable to use a method in which the amount of solvent during polymerization is within a range of 100 mass % or less when the total amount of the blended monomers is 100 mass % and the polymerization is performed while appropriately changing the solvent concentration during the polymerization.

[0217] More specifically, there can be exemplified a method in which 40 to 60 mass % is added at the initial stage of polymerization, the remaining 60 to 40 mass % is added during polymerization, and finally the amount of the solvent is adjusted to 100 mass % or less when the total amount of the monomers added is 100 mass %.

[0218] By adopting this method, the polymerization conversion rate can be improved, and the molecular weight distribution can be controlled. It is possible to obtain resins and resin compositions that have excellent injection moldability, reduce the content of fluorescent substances, and obtain good color tone even when making prisms with long optical path lengths. Therefore, it is preferred.

[0219] In solution polymerization, it is important to minimize the dissolved oxygen concentration in the polymerization solution, for example, the dissolved oxygen concentration is preferably a concentration of 10 ppm or less. The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter DO meter B-505 (manufactured by Iijima Electronics Industry Co., Ltd.). As a method for reducing the dissolved oxygen concentration, a method of bubbling an inert gas in the polymerization solution, a method of repeatedly pressurizing a container containing the polymerization solution with an inert gas to about 0.2 MPa before polymerization, and a method of passing an inert gas into a container containing the polymerization solution, etc. can be appropriately selected.

[0220] The polymerization temperature is not particularly limited as long as it is a temperature at which polymerization proceeds, but is preferably 70 to 180° C., more preferably 80 to 160° C., further preferably 90 to 150° C., and more preferably 100 to 150° C. From the viewpoint of productivity, it is preferably 70° C. or higher, and in order to suppress side reactions during polymerization and obtain a polymer of desired molecular weight and quality, it is preferably 180° C. or lower.

[0221] The polymerization time is not particularly limited as long as it is a time that can obtain a desired degree of polymerization at a desired conversion rate, but is preferably 2 to 15 hours, more preferably 3 to 12 hours, and even more preferably 4 to 10 hours from the viewpoint of productivity.

[0222] As the polymerization initiator, any initiator commonly used for free radical polymerization can be used, for example, organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-tert-butyl peroxide, lauroyl peroxide, benzoyl peroxide, tert-butyl peroxyisopropyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxyisononanoate, and 1,1-di(tert-butylperoxy)cyclohexane; azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate; etc.

[0223] These may be used alone or in combination of two or more.

[0224] The amount of the polymerization initiator added may be in the range of 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, based on 100% by mass of the total amount of monomers used in the polymerization.

[0225] The method of adding the polymerization initiator is not particularly limited as long as it is not a constant addition rate but a variable addition according to the residual monomer concentration in the polymerization solution, and it can be added continuously or intermittently. In the case of intermittent addition of the polymerization initiator, the time when it is not added does not take into account the amount added per unit time.

[0226] In this embodiment, the type and addition amount of the polymerization initiator, the polymerization temperature, etc. are preferably appropriately selected so that the ratio of the total amount of radicals generated by the polymerization initiator to the total amount of unreacted monomers remaining in the reaction system is always below a constant value.

[0227] By adopting these methods, the amount of oligomers and low molecular weight substances produced in the late stage of polymerization can be suppressed, and overheating during polymerization can be suppressed to achieve polymerization stability.

[0228] During the polymerization reaction, a chain transfer agent may be added as needed to carry out the polymerization.

[0229] As the chain transfer agent, the chain transfer agent used in the usual free radical polymerization can be used, for example, thiol compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate; halogen compounds such as carbon tetrachloride, dichloromethane, bromoform; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene; etc.

[0230] These may be used alone or in combination of two or more.

[0231] These chain transfer agents may be added at any stage as long as the polymerization reaction proceeds, and are not particularly limited.

[0232] The amount of the chain transfer agent added can be 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, when the total amount of the monomers used in the polymerization is 100% by mass.

[0233] As a method for recovering a polymer from a polymer solution obtained by solution polymerization, there can be mentioned a method of recovering a polymer product by separating the polymerization solvent and unreacted monomers through a process called a devolatilization process. Here, the devolatilization process refers to a process of removing volatile components such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure conditions.

[0234] In this embodiment, the content of unreacted N-substituted maleimide monomer contained in the polymerization solution containing methacrylic resin supplied to the devolatilization step is preferably controlled to be below a predetermined concentration. The details are as described in the above-mentioned "(2) Reduction of unreacted N-substituted maleimide at the end of polymerization". In addition to the above-mentioned methods, for example, the following methods may be used: a method of polymerizing by extending the polymerization time as much as possible in order to increase the conversion rate of the monomers, or by changing the addition rate of the polymerization initiator according to the concentration of unreacted monomers in the polymerization solution; a method of polymerizing while appropriately changing the solvent concentration during the polymerization; a method of supplementing other monomers highly reactive with the residual N-substituted maleimide monomer in the second half of the polymerization; a method of adding a compound highly reactive with N-substituted maleimide such as α-terpinene at the end of the polymerization, etc.

[0235] -Residual Amount of N-Substituted Maleimide Monomer-

[0236] As a method for obtaining the residual amount of N-substituted maleimide monomer remaining in a polymerization solution containing a methacrylic resin, for example, a portion of the polymerization solution can be collected and weighed, the sample is dissolved in chloroform, a 5% by mass solution is prepared, n-decane is added as an internal standard substance, and a gas chromatograph (manufactured by Shimadzu Corporation, GC-2010) is used to measure the concentration of the N-substituted maleimide monomer remaining in the sample, thereby obtaining the residual amount of the N-substituted maleimide monomer. As more specific measurement conditions, the conditions described in the examples described later can be used.

[0237] (3) Devolatilization method to reduce shear

[0238] As the device used in the devolatilization step, it is preferred to use a devolatilization device mainly composed of a heat exchanger and a decompression container and having no rotating part as its structure. By not providing a rotating part, shearing during devolatilization can be reduced, and a resin with lower fluorescence can be obtained.

[0239] Specifically, a devolatilization device can be used, wherein the devolatilization device is composed of a devolatilization tank having a heat exchanger disposed on its upper portion and a decompression unit attached to a decompression container having a size capable of devolatilization, and a discharge device such as a gear pump for discharging the devolatilized polymer.

[0240] Regarding the above-mentioned devolatilization device, the polymerization solution is supplied to a heat exchanger arranged on the upper part of the reduced pressure container and heated, for example, a multi-tube heat exchanger, a fin heat exchanger, a flat plate heat exchanger with a flat plate flow path and a heater, etc., and then supplied to a devolatilization tank under heating and reduced pressure to separate and remove the polymerization solvent, unreacted raw material mixture, polymerization by-products, etc. from the polymer. By using the devolatilization device without a rotating part as described above, it is possible to suppress the low molecular weight and fluorescent reaction by-products derived from the unreacted N-substituted maleimide, and the fluorescence intensity (the content of the fluorescent substance) in the methacrylic resin and the obtained resin prism can be controlled within a specified range, so it is preferred. In addition, a methacrylic resin with a good color tone can be obtained, so it is preferred.

[0241] As the above-mentioned device having a rotating part, there can be cited thin film evaporators such as Wiprene and Exeva manufactured by Kobelco Environmental Solutions Co., Ltd., KONTRO and inclined blade KONTRO manufactured by Hitachi, Ltd.; extruders with vent holes, etc.

[0242] In the devolatilization step of this embodiment, the shear rate applied to the polymerization solution is preferably set to 20 s -1 Below, more preferably set to 10s-1 Below, it is further preferred to use 0.1s -1 More than 10s -1 The following method is used to implement the process. By setting the shear rate to 0.1 s -1 The above-mentioned method can prevent the flow of the molten resin from being too slow, and can suppress the deterioration of the color tone caused by the increase of the residence time. -1 As a result, the generation of fluorescent reaction byproducts caused by shearing can be suppressed.

[0243] Here, the shear rate γ in the extruder is calculated by the following formula, for example.

[0244] γ=(π×D×N) / H

[0245] (Where D is the screw diameter (m), N is the screw speed per second, and H is the screw groove depth (m).)

[0246] In the case of a flat plate type flow channel, the shear velocity γ is calculated by the following formula.

[0247] γ=(6×Q) / (w×h 2 )

[0248] (Where Q represents the volume flow rate through the flat-plate flow path (m 3 / s), w represents the width of the flat-plate flow path (m), and h represents the distance between the flat plates (m).

[0249] In this embodiment, as the heat exchanger disposed on the upper part of the decompression container, a plate-type heat exchanger having a plate-type flow path and a heater is preferably used. More preferably, a plate-type heat exchanger having a plate-type flow path and a heater is used, wherein the plate-type flow path has a stacked structure having a plurality of slit-shaped flow paths having a rectangular cross-section on the same plane.

[0250] The polymer solution supplied to the devolatilization device is transferred from the center of the heat exchanger to the slit-shaped flow path to be heated. The heated polymer solution is supplied from the slit-shaped flow path to a reduced pressure container under reduced pressure integrated with the heat exchanger to be flash evaporated.

[0251] Such a devolatilization method is sometimes referred to as flash devolatilization, and in the present invention, it will also be referred to as flash devolatilization hereinafter.

[0252] It is also possible to adopt a method in which two or more devolatilization apparatuses are installed in series to perform devolatilization in two or more stages.

[0253] The temperature range of the heating by the heat exchanger with a devolatilization device can be set to 100°C to 300°C, preferably the glass transition temperature (Tg) of the methacrylic resin + 100°C to Tg + 160°C, and more preferably Tg + 110°C to Tg + 150°C. The temperature range of the heated and heat-insulated devolatilization tank can be set to 100°C to 300°C, preferably Tg + 100°C to Tg + 160°C, and more preferably Tg + 110°C to Tg + 150°C. When the temperature of the heat exchanger and the devolatilization tank is in this range, the thermal modification of the residual 2-amino-N-substituted succinimide can be suppressed, and the generation of fluorescent light-emitting substances can be suppressed, so it is preferred. In addition, it is preferred to effectively prevent the residual volatile components from increasing, and improve the thermal stability and product quality of the obtained methacrylic resin.

[0254] The vacuum degree in the devolatilization tank can be set to a range of 5 to 300 Torr, preferably 10 to 200 Torr. When the vacuum degree is 300 Torr or less, the unreacted monomer or the mixture of the unreacted monomer and the polymerization solvent can be effectively separated and removed, and the thermal stability and quality of the obtained thermoplastic copolymer will not be reduced. When the vacuum degree is 5 Torr or more, industrial implementation is easier.

[0255] The average residence time in the devolatilization tank may be 5 to 60 minutes, preferably 5 to 45 minutes. When the average residence time is within this range, the devolatilization can be performed efficiently and the coloration and decomposition caused by the thermal modification of the polymer can be suppressed, which is preferred.

[0256] The polymer recovered through the devolatilization step is processed into a pelletized form in a step called a granulation step.

[0257] In the granulation step, the molten resin is extruded in the form of strands by at least one conveying and granulating device selected from a gear pump having a porous die as an auxiliary device, a single-screw extruder, and a double-screw extruder, and processed into granules by cold cutting, air hot cutting, underwater strand cutting, and underwater cutting. From the viewpoint of controlling the generation of fluorescent reaction byproducts caused by shearing, it is preferred to select a conveying device with a low shearing speed instead of using an extruder.

[0258] In the present embodiment, in order to obtain a highly controlled resin composition, it is preferred to adopt a granulation method that allows the resin composition in a molten state at a high temperature to be cooled and solidified quickly without contacting the air as much as possible.

[0259] In this case, it is more preferable to lower the molten resin temperature within a possible range, and to reduce the residence time from the porous die outlet to the cooling water surface as much as possible, and to perform granulation under feasible conditions at a higher temperature than possible.

[0260] For example, the molten resin temperature is preferably 220 to 280°C, more preferably 230 to 270°C. The residence time from the porous die outlet to the cooling water surface is preferably within 5 seconds, more preferably within 3 seconds. The cooling water temperature is preferably in the range of 30 to 80°C, more preferably 40 to 60°C.

[0261] By carrying out the process within these ranges of the molten resin temperature and the cooling water temperature, a methacrylic resin and a composition thereof with less coloration and a low water content can be obtained, which is preferred.

[0262] From the viewpoint of thermal stability and product quality, the content of the monomers remaining in the methacrylic resin after the devolatilization step is preferably as small as possible. Specifically, the content of the methacrylate monomer is preferably 3000 mass ppm or less, and more preferably 2000 mass ppm or less. The content of the N-substituted maleimide monomer is preferably 200 mass ppm or less, and more preferably 100 mass ppm or less in total.

[0263] The content of the residual polymerization solvent is preferably 500 ppm by mass or less, and more preferably 300 ppm by mass or less.

[0264] -Method for producing methacrylic acid resin containing glutarimide structural units-

[0265] As a method for producing a methacrylic resin having a glutarimide-based structural unit in the main chain, any polymerization method of bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, and emulsion polymerization can be cited, and suspension polymerization, bulk polymerization, and solution polymerization are preferred, and solution polymerization is more preferred.

[0266] In the production method of the present embodiment, as a polymerization method, for example, any of a batch polymerization method, a semi-batch method, and a continuous polymerization method can be used.

[0267] Among the production methods in this embodiment, a method of polymerizing monomers by radical polymerization is preferred.

[0268] The methacrylic resin having a glutarimide structural unit in the main chain may be, for example, a methacrylic resin having a glutarimide structural unit described in JP-A-2006-249202, JP-A-2007-009182, JP-A-2007-009191, JP-A-2011-186482, International Publication No. 2012 / 114718, etc., and may be formed by the method described in the said publications.

[0269] Hereinafter, as an example of a method for producing a methacrylic resin having a glutarimide structural unit, a case of producing the methacrylic resin by batch radical polymerization using a solution polymerization method will be specifically described.

[0270] First, a (meth)acrylate polymer is produced by polymerizing a (meth)acrylate such as methyl methacrylate. When a methacrylic resin having a glutarimide structural unit contains an aromatic vinyl unit, a (meth)acrylate and an aromatic vinyl (e.g., styrene) are copolymerized to produce a (meth)acrylate-aromatic vinyl copolymer.

[0271] Examples of the solvent used in the polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; and ketones such as methyl ethyl ketone and methyl isobutyl ketone.

[0272] These solvents may be used alone or in combination of two or more.

[0273] The amount of solvent during polymerization is not particularly limited as long as it is an amount that allows polymerization to proceed, does not cause precipitation of copolymers and monomers used during production, and can be easily removed. For example, when the total amount of the monomers to be matched is 100% by mass, it is preferably 10 to 200% by mass, more preferably 25 to 200% by mass, further preferably 50 to 200% by mass, and further more preferably 50 to 150% by mass.

[0274] The polymerization temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but is preferably 50 to 200° C., more preferably 80 to 200° C., further preferably 90 to 150° C., further more preferably 100 to 140° C., and further preferably 100 to 130° C. From the viewpoint of productivity, it is preferably 70° C. or higher, and in order to suppress side reactions during polymerization and obtain a polymer of a desired molecular weight and quality, it is preferably 180° C. or lower.

[0275] The polymerization time is not particularly limited as long as the intended conversion rate is achieved, but is preferably 0.5 to 15 hours, more preferably 2 to 12 hours, and even more preferably 4 to 10 hours from the viewpoint of productivity.

[0276] During the polymerization reaction, a polymerization initiator or a chain transfer agent may be added as needed to carry out the polymerization.

[0277] The polymerization initiator is not particularly limited, and for example, the polymerization initiators disclosed in the method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used.

[0278] These polymerization initiators may be used alone or in combination of two or more.

[0279] These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress.

[0280] The amount of the polymerization initiator added is not particularly limited and may be appropriately set according to the combination of monomers, reaction conditions, etc., but can be 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, based on 100% by mass of the total amount of monomers used in the polymerization.

[0281] As the chain transfer agent, a chain transfer agent used in ordinary radical polymerization can be used. For example, a chain transfer agent disclosed in the method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used.

[0282] These may be used alone or in combination of two or more.

[0283] These chain transfer agents may be added at any stage as long as the polymerization reaction proceeds, and are not particularly limited.

[0284] The amount of the chain transfer agent added is not particularly limited as long as the desired degree of polymerization can be obtained under the polymerization conditions used, but is preferably 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, based on 100% by mass of the total amount of monomers used in the polymerization.

[0285] The method for adding a suitable polymerization initiator and a chain transfer agent in the polymerization step may be, for example, the method described in the method for producing a methacrylic resin having a structural unit derived from the above-mentioned N-substituted maleimide monomer.

[0286] The dissolved oxygen concentration in the polymerization solution may be, for example, the value disclosed in the method for producing a methacrylic resin having a structural unit derived from the above-mentioned N-substituted maleimide monomer.

[0287] Next, the (meth)acrylate polymer or the methacrylate-aromatic vinyl copolymer is reacted with an imidizing agent to perform an imidization reaction (imidization step), thereby producing a methacrylic resin having a glutarimide structural unit.

[0288] The imidizing agent is not particularly limited as long as it is an imidizing agent that can generate the glutarimide structural unit represented by the general formula (3).

[0289] As the imidizing agent, specifically, ammonia or a primary amine can be used. Examples of the primary amine include aliphatic hydrocarbon group-containing primary amines such as methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, and n-hexylamine; alicyclic hydrocarbon group-containing primary amines such as cyclohexylamine; and the like.

[0290] Among the above-mentioned imidizing agents, ammonia, methylamine, and cyclohexylamine are preferably used in view of cost and physical properties, and methylamine is particularly preferably used.

[0291] In the imidization step, the content of the glutarimide structural unit in the obtained methacrylic resin having a glutarimide structural unit can be adjusted by adjusting the addition ratio of the imidization agent.

[0292] The method for carrying out the imidization reaction is not particularly limited, and a conventionally known method can be used. For example, the imidization reaction can be carried out by using an extruder or a batch reaction tank.

[0293] The extruder is not particularly limited, and for example, a single-screw extruder, a twin-screw extruder, a multi-screw extruder, etc. can be used.

[0294] Among them, a twin-screw extruder is preferably used. The twin-screw extruder can promote mixing of the base polymer and the imidizing agent.

[0295] Examples of the twin-screw extruder include a non-intermeshing co-rotating type, an intermeshing co-rotating type, a non-intermeshing counter-rotating type, and an intermeshing counter-rotating type.

[0296] The extruders exemplified above may be used alone or in plurality connected in series.

[0297] It is particularly preferred that the extruder used be equipped with a vent capable of reducing the pressure to below atmospheric pressure, because this can remove the imidization agent, byproducts such as methanol, and monomers produced by the reaction.

[0298] When producing a methacrylic resin having a glutarimide structural unit, in addition to the above-mentioned imidization step, an esterification step of treating the carboxyl group of the resin with an esterifying agent such as dimethyl carbonate may be included. In this case, a catalyst such as trimethylamine, triethylamine, or tributylamine may be used in combination for the treatment.

[0299] The esterification step can be performed similarly to the above-mentioned imidization step by using, for example, an extruder or a batch reaction tank.

[0300] In order to remove excess esterification agent, byproducts such as methanol, or monomers, it is preferred that the apparatus used be equipped with a vent capable of reducing the pressure to below atmospheric pressure.

[0301] The methacrylic resin that has undergone the imidization step and the esterification step as needed is melted and extruded in the form of strands from an extruder equipped with a multi-hole die, and processed into pellets by cold cutting, air hot cutting, underwater strand cutting, underwater cutting, etc.

[0302] In order to reduce the amount of foreign matter in the resin, it is also preferable to use a method of dissolving a methacrylic resin in an organic solvent such as toluene, methyl ethyl ketone, or dichloromethane, filtering the obtained methacrylic resin solution, and then devolatilizing the organic solvent.

[0303] From the viewpoint of reducing the fluorescence intensity (the content of the fluorescent substance), it is preferred to imidize the polymerization solution after the completion of the polymerization in a batch reaction tank without using a twin-screw extruder that is subjected to shearing force.

[0304] The imidization reaction is preferably carried out at 130 to 250° C., more preferably at 150 to 230° C., and further preferably at 170 to 190° C. The reaction time is preferably 10 minutes to 5 hours, and more preferably 30 minutes to 2 hours.

[0305] From the viewpoint of reducing the fluorescence intensity, it is preferred that after the imidization step, and if necessary, after the esterification step, devolatilization is performed by the devolatilization method (3) with reduced shear described in the method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer, and then granulation is performed.

[0306] -Method for producing methacrylic resin containing lactone ring structural unit-

[0307] As a method for producing a methacrylic resin having a lactone ring structural unit in the main chain, a method of forming a lactone ring structure by a cyclization reaction after polymerization can be used. Preferably, the monomer is polymerized by free radical polymerization using a solution polymerization method using a solvent while promoting the cyclization reaction.

[0308] In the production method of the present embodiment, as a polymerization method, for example, any of a batch polymerization method, a semi-batch method, and a continuous polymerization method can be used.

[0309] The methacrylic resin having a lactone ring structural unit in the main chain can be formed by the method described in, for example, JP-A-2001-151814, JP-A-2004-168882, JP-A-2005-146084, JP-A-2006-96960, JP-A-2006-171464, JP-A-2007-63541, JP-A-2007-297620, JP-A-2010-180305, etc.

[0310] Hereinafter, as an example of a method for producing a methacrylic resin having a lactone ring structural unit, a case of producing the methacrylic resin by batch-wise radical polymerization using a solution polymerization method will be specifically described.

[0311] As a method for producing a methacrylic resin having a lactone ring structural unit, a method of forming a lactone ring structure by a cyclization reaction after polymerization can be used, and solution polymerization using a solvent to promote the cyclization reaction is preferred.

[0312] Examples of the solvent used in the polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; and ketones such as methyl ethyl ketone and methyl isobutyl ketone.

[0313] These solvents may be used alone or in combination of two or more.

[0314] The amount of solvent during polymerization is not particularly limited as long as the polymerization proceeds and gelation is suppressed. For example, when the total amount of the monomers to be formulated is 100 mass %, it is preferably 50 to 200 mass %, more preferably 100 to 200 mass %.

[0315] In order to fully suppress the gelation of the polymer solution and promote the cyclization reaction after the polymerization, it is preferred to polymerize in a manner such that the concentration of the polymer generated in the reaction mixture obtained after the polymerization becomes 50% by mass or less. In addition, it is preferred to appropriately add a polymerization solvent to the reaction mixture and control in a manner such that the above-mentioned concentration becomes 50% by mass or less.

[0316] The method of appropriately adding the polymerization solvent to the reaction mixture is not particularly limited, and for example, the polymerization solvent may be added continuously or intermittently.

[0317] The polymerization solvent added may be a single solvent or a mixed solvent of two or more solvents.

[0318] The polymerization temperature is not particularly limited as long as it is a temperature at which polymerization proceeds, but is preferably 50 to 200°C, more preferably 80 to 180°C, from the viewpoint of productivity.

[0319] The polymerization time is not particularly limited as long as the intended conversion rate is satisfied, but is preferably 0.5 to 10 hours, more preferably 1 to 8 hours, from the viewpoint of productivity and the like.

[0320] During the polymerization reaction, a polymerization initiator or a chain transfer agent may be added as needed to carry out the polymerization.

[0321] The polymerization initiator is not particularly limited, and for example, the polymerization initiators disclosed in the method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used.

[0322] These polymerization initiators may be used alone or in combination of two or more.

[0323] These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress.

[0324] The amount of the polymerization initiator added is not particularly limited and may be appropriately set depending on the combination of monomers, reaction conditions, etc., but can be 0.05 to 1% by mass when the total amount of the monomers used in the polymerization is 100% by mass.

[0325] As the chain transfer agent, a chain transfer agent used in ordinary radical polymerization can be used. For example, a chain transfer agent disclosed in the method for producing a methacrylic resin having a structural unit derived from an N-substituted maleimide monomer can be used.

[0326] These may be used alone or in combination of two or more.

[0327] These chain transfer agents may be added at any stage as long as the polymerization reaction proceeds, and are not particularly limited.

[0328] The amount of the chain transfer agent added is not particularly limited as long as the desired degree of polymerization can be obtained under the polymerization conditions used, but is preferably 0.05 to 1% by mass based on 100% by mass of the total amount of monomers used in the polymerization.

[0329] The method for adding a polymerization initiator and a chain transfer agent in the polymerization step may be, for example, the method described in the method for producing a methacrylic resin having a structural unit derived from the above-mentioned N-substituted maleimide monomer.

[0330] The dissolved oxygen concentration in the polymerization solution may be, for example, the value disclosed in the method for producing a methacrylic resin having a structural unit derived from the above-mentioned N-substituted maleimide monomer.

[0331] The methacrylic resin having a lactone ring structural unit in this embodiment can be obtained by performing a cyclization reaction after the completion of the above-mentioned polymerization reaction. Therefore, it is preferred to provide the lactone cyclization reaction in a state containing a solvent without removing the polymerization solvent from the polymerization reaction solution.

[0332] The copolymer obtained by polymerization is subjected to heat treatment to cause a cyclization condensation reaction between the hydroxyl group (hydroxyl group) and the ester group present in the molecular chain of the copolymer, thereby forming a lactone ring structure.

[0333] In the heat treatment for forming the lactone ring structure, a reaction apparatus equipped with a vacuum device or a devolatilizer for removing alcohol that may be by-produced by the cyclocondensation, an extruder equipped with a devolatilizer, or the like may be used.

[0334] When the lactone ring structure is formed, a heat treatment may be performed using a cyclization condensation catalyst as needed in order to promote the cyclization condensation reaction.

[0335] Specific examples of the cyclization condensation catalyst include, for example, monoalkyl phosphites, dialkyl phosphites or triesters such as methyl phosphite, ethyl phosphite, phenyl phosphite, dimethyl phosphite, diethyl phosphite, diphenyl phosphite, trimethyl phosphite and triethyl phosphite; monoalkyl phosphites, dialkyl phosphites or trialkyl phosphites such as methyl phosphate, ethyl phosphate, 2-ethylhexyl phosphate, octyl phosphate, isodecyl phosphate, lauryl phosphate, stearyl phosphate, isostearyl phosphate, dimethyl phosphate, diethyl phosphate, di-2-ethylhexyl phosphate, diisodecyl phosphate, dilauryl phosphate, distearyl phosphate, diisostearyl phosphate, trimethyl phosphate, triethyl phosphate, triisodecyl phosphate, trilauryl phosphate, tristearyl phosphate and triisostearyl phosphate; organic zinc compounds such as zinc acetate, zinc propionate and octyl zinc; and the like.

[0336] These may be used alone or in combination of two or more.

[0337] The amount of the cyclization condensation catalyst used is not particularly limited, but is, for example, preferably 0.01 to 3% by mass, more preferably 0.05 to 1% by mass, based on 100% by mass of the methacrylic resin.

[0338] When the amount of the catalyst used is 0.01% by mass or more, the reaction rate of the cyclocondensation reaction is effectively increased, and when the amount of the catalyst used is 3% by mass or less, the coloring of the obtained polymer and the difficulty of crosslinking the polymer to form a melt are effectively prevented.

[0339] The timing of adding the cyclization condensation catalyst is not particularly limited, and the catalyst may be added, for example, at the initial stage of the cyclization condensation reaction, during the reaction, or at both times.

[0340] When the cyclization condensation reaction is carried out in the presence of a solvent, devolatilization may be carried out simultaneously.

[0341] The apparatus used when the cyclocondensation reaction and the devolatilization step are carried out simultaneously is not particularly limited, and may be a devolatilization apparatus composed of a heat exchanger and a devolatilization tank, or an extruder with a vent. Preferably, the devolatilization apparatus and the extruder are arranged in series, and more preferably, a twin-screw extruder with a vent.

[0342] As the vented twin-screw extruder to be used, a vented extruder having a plurality of vent holes is preferred.

[0343] When using an extruder with a vent hole, the reaction treatment temperature is preferably 150 to 350° C., more preferably 200 to 300° C. When the reaction treatment temperature is lower than 150° C., the cyclocondensation reaction becomes insufficient and the residual volatile components increase. On the contrary, when the reaction treatment temperature is higher than 350° C., the obtained polymer may be colored or decomposed.

[0344] The vacuum degree when using an extruder with a vent hole is preferably 10 to 500 Torr, and more preferably 10 to 300 Torr. When the vacuum degree is greater than 500 Torr, volatile components may easily remain. On the contrary, when the vacuum degree is less than 10 Torr, industrial implementation may become difficult.

[0345] When the above-mentioned cyclocondensation reaction is carried out, it is also preferred to add an alkaline earth metal and / or amphoteric metal salt of an organic acid during granulation for the purpose of deactivating the remaining cyclocondensation catalyst.

[0346] As the alkaline earth metal and / or amphoteric metal salt of an organic acid, for example, calcium acetoacetate, calcium stearate, zinc acetate, zinc octylate, zinc 2-ethylhexanoate, etc. can be used.

[0347] After the cyclocondensation reaction step, the methacrylic resin is melted and extruded in a strand form from an extruder equipped with a multi-hole die, and processed into a pellet form by a cold cutting method, an air hot cutting method, an underwater strand cutting method, or an underwater cutting method.

[0348] The lactonization for forming the lactone ring structural unit may be performed after the production of the resin and before the production of the resin composition (described later), or may be performed during the production of the resin composition together with melt kneading of the resin and components other than the resin.

[0349] From the viewpoint of reducing the fluorescence intensity (the content of the fluorescent substance), it is preferred that the polymerization solution after the polymerization is subjected to lactone cyclization in a batch reaction tank without using a twin-screw extruder subjected to shearing force. From the viewpoint of reducing the fluorescence intensity, it is preferred that after the lactone cyclization step, the product is devolatilized by the devolatilization method (3) for reducing shearing described in the method for producing a methacrylic resin having a structural unit derived from the above-mentioned N-substituted maleimide monomer, and then granulated.

[0350] [additive]

[0351] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment may contain various additives within the above-mentioned range not significantly impairing the effects of the present invention.

[0352] There are no particular restrictions on the additives, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins, paraffin-based processing oils, cycloparaffin-based processing oils, aromatic processing oils, paraffins, organopolysiloxanes, softeners / plasticizers such as mineral oils, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants; organic phosphorus compounds such as phosphites, phosphonites, and phosphates, other additives, or mixtures thereof, and the like.

[0353] -Antioxidants-

[0354] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment preferably contains an antioxidant for suppressing deterioration and coloration during molding or use.

[0355] Examples of the antioxidant include hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants, but the antioxidant is not limited to these antioxidants.

[0356] These antioxidants may be used alone or in combination of two or more.

[0357] From the viewpoint of improving thermal stability and suppressing molding defects, it is preferred to use a plurality of thermal stabilizers in combination. For example, it is preferred to use at least one selected from phosphorus-based antioxidants and sulfur-based antioxidants in combination with a hindered phenol-based antioxidant.

[0358] Examples of the hindered phenol antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], diethylenethiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the like. ester], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, etc., but are not limited to these hindered phenol antioxidants.

[0359] Particularly preferred are pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate.

[0360] As the hindered phenol antioxidant of the antioxidant, a commercially available phenol antioxidant can be used. Examples of such commercially available phenol antioxidants include Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), and Irganox 1340 (Irganox 1340: 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF). 3114 (Ilganox 3114: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Ilganox 3125, manufactured by BASF), ADK STAB AO-60 (Adekas Stab AO-60) (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], manufactured by ADEKA), ADK STAB AO-80 (Adeks Stab AO-80) (3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (Sianox 1790, manufactured by SITECH), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer GS: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (Sumilizer GM: 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), vitamin E (manufactured by Eisai Co., Ltd.), etc., but are not limited to these.

[0361] Among these commercially available phenolic antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin, Irganox 1010, ADK STAB AO-60, ADK STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred.

[0362] These may be used alone or in combination of two or more.

[0363] Examples of the phosphorus antioxidants of the antioxidants include tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethylphosphite, tetrakis(2,4-di-tert-butylphenyl)(1,1-biphenyl)-4,4'-diyl diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)quaternary Pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, tetrakis(2,4-tert-butylphenyl)(1,1-biphenyl)-4,4'-diyl diphosphite, di-tert-butyl-m-tolylphosphite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinylcycloheptyl)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, etc., but are not limited to these.

[0364] As the phosphorus-based antioxidant, a commercially available phosphorus-based antioxidant may be used. Examples of such commercially available phosphorus-based antioxidants include Irgafos 168 (Irgafos 168: tris(2,4-di-tert-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphocycloheptan-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl phosphite, manufactured by BASF), and ADK. STAB-229K (ADK STAB 329K, ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, ADEKA), ADK STAB PEP-36A (ADK STAB PEP-36A, ADEKA), ADK STAB PEP-8 (ADK STAB PEP-8, ADEKA), ADK STAB HP-10 (ADK STAB HP-10, ADEKA), ADK STAB 2112 (ADK STAB 2112, ADEKA), ADK STAB 1178 (ADK STAB 1178, ADEKA), ADK STAB 1500 (アデカスタブ1500, made by ADEKA), Sandstab P-EPQ (made by CLARIANT, クラリアント), Weston 618 (ウェストン618, made by GE), Weston 619G (ウェストン619G, made by GE), Ultranox 626 (ウルトラノックス626, made by GE), Sumilizer GP (Sumilyzer GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinane)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical), HCA (9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide, manufactured by Sanko Co., Ltd.), etc., but are not limited to these.

[0365] Among these commercially available phosphorus-based antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred from the viewpoint of the effect of imparting thermal stability to the resin and the effect of combined use with a plurality of antioxidants. ADK STAB PEP-36A and ADK STAB PEP-36A are particularly preferred.

[0366] These phosphorus-based antioxidants may be used alone or in combination of two or more.

[0367] Examples of the sulfur-based antioxidants of the antioxidant include 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ADKSTAB AO-412S (Adeka Stab AO-412S, manufactured by ADEKA), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (KEMINOX PLS, manufactured by CHEMIPRO Chemicals Co., Ltd.), ditridecyl 3,3'-thiodipropionate (AO-503, manufactured by ADEKA), etc., but are not limited to these.

[0368] Among these commercially available sulfur antioxidants, ADK STAB AO-412S and KEMINOX PLS are preferred from the viewpoint of the effect of imparting thermal stability to the resin, the effect of combined use with a plurality of antioxidants, and the viewpoint of handling properties.

[0369] These sulfur-based antioxidants may be used alone or in combination of two or more.

[0370] The content of the antioxidant may be an amount that can obtain the effect of improving thermal stability. When the content is excessive, problems such as bleeding may occur during processing. Therefore, it is preferably 5 mass% or less, more preferably 3 mass% or less, further preferably 1 mass% or less, further more preferably 0.8 mass% or less, further preferably 0.01 to 0.8 mass%, particularly preferably 0.01 to 0.5 mass%, based on 100 mass% of the methacrylic resin.

[0371] There is no particular limitation on the timing of adding the antioxidant, and examples thereof include: a method of adding the antioxidant to the monomer solution before polymerization and then starting polymerization; a method of adding the antioxidant to the polymer solution after polymerization and mixing and then supplying the antioxidant to the devolatilization step; a method of adding the antioxidant to the molten polymer after devolatilization and then mixing and then granulating the polymer; a method of adding the antioxidant to the granulated pellets after devolatilization and granulation and then mixing the granules, etc. Among these, from the viewpoint of preventing thermal degradation and coloration in the devolatilization step, a method of adding the antioxidant to the polymer solution after polymerization and mixing and then supplying the antioxidant to the devolatilization step is preferred.

[0372] -Hindered amine light stabilizer-

[0373] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment may contain a hindered amine-based light stabilizer.

[0374] The hindered amine light stabilizer is not particularly limited, but is preferably a compound containing three or more ring structures. Here, the ring structure is preferably at least one selected from the group consisting of an aromatic ring, an aliphatic ring, an aromatic heterocycle and a non-aromatic heterocycle. When a compound has two or more ring structures, these ring structures may be the same or different from each other.

[0375] As hindered amine light stabilizers, for example, specifically, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, N,N'-bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, (2,2,6,6-tetramethyl-4-piperidinyl)-N,N'-dicarboxylic acid hexamethylene diamine, dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylene diamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine condensation product, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylene diamine

[0063] 1,2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3, 9-diethanol, a reaction product of 2,2,6,6-tetramethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate, etc., but are not limited to these.

[0376] Among them, preferred are bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate containing three or more ring structures, polycondensates of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl]-}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}], the reaction products of 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and the reaction products of 2,2,6,6-tetramethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol.

[0377] The content of the hindered amine light stabilizer may be an amount that can obtain the effect of improving the light stability. When the content is excessive, problems such as bleeding may occur during processing. Therefore, it is preferably 5 mass% or less, more preferably 3 mass% or less, further preferably 1 mass% or less, further more preferably 0.8 mass% or less, further preferably 0.01 to 0.8 mass%, and particularly preferably 0.01 to 0.5 mass%, based on 100 mass% of the methacrylic resin.

[0378] --UV absorber--

[0379] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment may contain an ultraviolet absorber.

[0380] The ultraviolet absorber is not particularly limited, but preferably has a maximum absorption wavelength of 280 to 380 nm, and examples thereof include benzotriazole compounds, benzotriazine compounds, benzophenone compounds, oxybenzophenone compounds, benzoate compounds, phenol compounds, oxazole compounds, cyanoacrylate compounds, and benzoxazinone compounds.

[0381] Examples of the benzotriazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1 ,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidomethyl)phenol, 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propanoic acid methyl ester reaction products with polyethylene glycol 300, 2-(2H-benzotriazol-2-yl)-6-(straight-chain and branched dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 branched and straight chain alkyl esters.

[0382] Among these, benzotriazole compounds having a molecular weight of 400 or more are preferred. For example, in the case of commercially available products, Kemisorb (registered trademark) 2792 (manufactured by CHEMIPRO Chemicals), ADK STAB (registered trademark) LA31 (manufactured by ADEKA Corporation), Tinuvin (registered trademark) 234 (manufactured by BASF), etc. can be cited.

[0383] Examples of the benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specifically, examples include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine. 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4- 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine,6-Tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6 -Tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6 -Tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5- Triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, etc.

[0384] As the benzotriazine-based compound, commercially available products can be used, for example, Kemisorb 102 (manufactured by Kemisorb Chemicals Co., Ltd.), LA-F70 (manufactured by ADEKA Corporation), LA-46 (manufactured by ADEKA Corporation), Tinuvin 405 (manufactured by BASF), Tinuvin 460 (manufactured by BASF), Tinuvin 479 (manufactured by BASF), Tinuvin 1577FF (manufactured by BASF), etc.

[0385] Among them, from the perspective of high compatibility with acrylic resins and excellent ultraviolet absorption properties, it is more preferable to use an ultraviolet absorber having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkoxy-2-hydroxypropoxy)-5-α-cumylphenyl]-s-triazine skeleton ("alkoxy" refers to a long-chain alkoxy group such as octyloxy, nonyloxy, and decyloxy).

[0386] As the ultraviolet absorber, particularly from the viewpoint of compatibility with the resin and volatility during heating, benzotriazole compounds and benzotriazine compounds having a molecular weight of 400 or more are preferred. Furthermore, from the viewpoint of suppressing decomposition due to heating during extrusion processing of the ultraviolet absorber itself, benzotriazine compounds are particularly preferred.

[0387] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, further preferably 130° C. or higher, and further preferably 160° C. or higher.

[0388] The above-mentioned ultraviolet absorber preferably has a weight loss rate of 50% or less, more preferably 30% or less, further preferably 15% or less, further more preferably 10% or less, and further preferably 5% or less when the temperature is increased from 23°C to 260°C at a rate of 20°C / min.

[0389] These ultraviolet absorbers may be used alone or in combination of two or more. By using two ultraviolet absorbers having different structures in combination, ultraviolet rays in a wide wavelength range can be absorbed.

[0390] The content of the ultraviolet absorber is not particularly limited as long as it does not hinder heat resistance, moisture and heat resistance, thermal stability and molding processability and exerts the effect of the present invention. It is preferably 0.1 to 5% by mass, preferably 0.2 to 4% by mass, more preferably 0.25 to 3% by mass, and further preferably 0.3 to 3% by mass relative to 100% by mass of the methacrylic resin. When it is within this range, the balance between ultraviolet absorption performance and molding properties is excellent.

[0391] --Release Agent--

[0392] The resin composition constituting the resin prism for polarization beam splitter of the present embodiment may contain a release agent. Examples of the release agent include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon lubricants, alcohol lubricants, polyalkylene glycols, carboxylates, and hydrocarbon paraffin mineral oils.

[0393] The fatty acid ester that can be used as the release agent is not particularly limited, and conventionally known fatty acid esters can be used.

[0394] As fatty acid esters, for example, ester compounds of fatty acids having 12 to 32 carbon atoms such as lauric acid, palmitic acid, margaric acid, stearic acid, oleic acid, arachidic acid, and behenic acid and monovalent aliphatic alcohols such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, or polyvalent aliphatic alcohols such as glycerol, pentaerythritol, dipentaerythritol, and sorbitan; complex ester compounds of fatty acids and polyvalent organic acids and monovalent aliphatic alcohols or polyvalent aliphatic alcohols, etc. can be used.

[0395] Examples of such fatty acid esters include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glyceryl monocaprylate, glyceryl monocaprate, glyceryl monolaurate, glyceryl monopalmitate, glyceryl dipalmitate, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, glyceryl monooleate, glyceryl dioleate, glyceryl trioleate, glyceryl monolinoleate, glyceryl monobehenate, glyceryl mono-12-hydroxystearate, glyceryl di-12-hydroxystearate, glyceryl tri-12-hydroxystearate, glyceryl diacetyl monostearate, glyceryl citric acid fatty acid ester, pentaerythritol adipic acid stearate, montanic acid partially saponified ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate.

[0396] These fatty acid esters may be used alone or in combination of two or more.

[0397] Examples of commercially available products include the RIKEMAL series, POEM series, RIKESTAR series, and RIKEMASTER series manufactured by Riken Vita Co., Ltd., and the EXCEL series, RHEODOL series, EXCEPARL series, and COCONAD series manufactured by Kao Corporation. More specifically, RIKEMAL S-100, RIKEMAL H-100, and POEM RIKEMAL S-200 (リケマールS-200), POEM B-200 (ポエムB-200), RIKESTAR EW-200 (リケスターEW-200), RIKESTAR EW-400 (リケスターEW-400), EXCELS-95 (エキセルS-95), RHEODOL MS-50 (レオドールMS-50), etc.

[0398] The fatty acid amide is not particularly limited, and conventionally known fatty acid amides can be used.

[0399] Examples of fatty acid amides include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; hydroxymethyl amides such as hydroxymethyl stearic acid amide and hydroxymethyl behenic acid amide; methylene bis stearic acid amide, ethylene bis capric acid amide, ethylene bis lauric acid amide, and ethylene bis stearic acid amide (ethylene bis stearic acid amide); Saturated fatty acid bisamides such as bisstearylamide, ethylene bisisostearylamide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide, etc.

[0400] These fatty acid amides may be used alone or in combination of two or more.

[0401] As commercially available products, for example, DIAMIDO series (manufactured by Nippon Chemical Industry Co., Ltd.), amide series (manufactured by Nippon Chemical Industry Co., Ltd.), Nikka Amide series (manufactured by Nippon Chemical Industry Co., Ltd.), methylolamide series, bisamide series, Suripakkusu series (manufactured by Nippon Chemical Industry Co., Ltd.), Kao wax series (manufactured by Kao Corporation), fatty acid amide series (manufactured by Kao Corporation), ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industries, Ltd.), etc. can be mentioned.

[0402] Fatty acid metal salt refers to a metal salt of a higher fatty acid, and examples thereof include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexanoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, lithium 12-hydroxystearate, and the like. Among them, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred from the viewpoint of making the obtained transparent resin composition excellent in processability and extremely excellent in transparency.

[0403] As an example of commercially available products, there can be mentioned SZ series, SC series, SM series, SA series and the like manufactured by Sakai Chemical Industry Co., Ltd.

[0404] When the fatty acid metal salt is used, the content is preferably 0.2% by mass or less based on 100% by mass of the resin composition from the viewpoint of maintaining transparency.

[0405] The above-mentioned release agents may be used alone or in combination of two or more.

[0406] As the release agent to be used, it is preferable that the decomposition starting temperature is 200° C. or higher. Here, the decomposition starting temperature can be measured by the temperature at which the mass decreases by 1% based on TGA.

[0407] The content of the release agent may be an amount that can obtain the effect as a release agent. If the content is excessive, problems such as bleeding or poor extrusion due to screw slip may occur during processing. Therefore, it is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, further more preferably 0.8% by mass or less, further preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass, relative to 100% by mass of the methacrylic resin. When added in the above range, there is a tendency to suppress poor demolding during injection molding while suppressing the decrease in transparency caused by the addition of the release agent. Therefore, the above situation is preferred.

[0408] -Other thermoplastic resins-

[0409] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment may contain other thermoplastic resins in addition to the methacrylic resin for the purpose of adjusting the birefringence and improving the flexibility, unless the object of the present invention is impaired.

[0410] As other thermoplastic resins, for example, polyacrylates such as polybutyl acrylate; styrene polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene block copolymer; in addition, for example, 3-4 layer structure acrylic rubber particles described in Japanese Unexamined Patent Publication No. 59-202213, Japanese Unexamined Patent Publication No. 63-27516, Japanese Unexamined Patent Publication No. 51-129449, Japanese Unexamined Patent Publication No. 52-56150, etc.; rubber polymers disclosed in Japanese Unexamined Patent Publication No. 60-17406 and Japanese Unexamined Patent Publication No. 8-245854; methacrylic rubber-containing graft copolymer particles obtained by multi-stage polymerization described in International Publication No. 2014-002491; etc.

[0411] Among them, from the viewpoint of obtaining good optical and mechanical properties, preferred are styrene-acrylonitrile copolymers and rubber-containing graft copolymer particles having a graft portion on the surface layer, wherein the graft portion is composed of a composition compatible with a methacrylic resin containing a structural unit X having a ring structure on the main chain.

[0412] The average particle size of the acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the film obtained from the composition of this embodiment.

[0413] When the methacrylic resin is contained in an amount of 100% by mass, the content of the other thermoplastic resin is preferably 0 to 50% by mass, and more preferably 0 to 25% by mass.

[0414] [Method for producing resin composition]

[0415] As a method for manufacturing the resin composition constituting the resin prism for the polarization beam splitter of the present embodiment, there is no particular limitation as long as a composition that satisfies the conditions of the present invention can be obtained. For example, a method of mixing using a mixer such as an extruder, a heating roller, a kneader, a roller mixer, a Banbury mixer, etc. can be cited. Among them, from the aspect of productivity, mixing based on an extruder is preferred. The mixing temperature can be based on the preferred processing temperature of the polymer constituting the methacrylic resin and the other mixed resins, and can be in the range of 140 to 300°C as a benchmark, preferably in the range of 180 to 280°C. In addition, for the purpose of reducing volatile components, it is preferred to set a vent hole in the extruder.

[0416] Here, in the resin composition constituting the resin prism for a polarization beam splitter of the present embodiment, the amount of residual solvent (residual solvent amount) is preferably less than 1000 mass ppm, more preferably less than 800 mass ppm, and further preferably less than 700 mass ppm.

[0417] Here, the residual solvent refers to the polymerization solvent used during polymerization (except alcohols) and the solvent used when the resin obtained by the polymerization is dissolved again to make a solution. Specifically, as the polymerization solvent, aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; polar solvents such as dimethylformamide and 2-methylpyrrolidone; etc., as the solvent used for re-dissolution, toluene, methyl ethyl ketone, dichloromethane, etc. can be exemplified.

[0418] The resin composition constituting the resin prism for a polarization beam splitter according to the present embodiment preferably has a residual alcohol content (residual alcohol content) of less than 500 mass ppm, more preferably less than 400 mass ppm, and further preferably less than 350 mass ppm.

[0419] Here, the residual alcohol refers to an alcohol produced as a by-product by the cyclization condensation reaction, and specific examples thereof include aliphatic alcohols such as methanol, ethanol, and isopropanol.

[0420] The residual solvent amount and the residual alcohol amount can be measured by gas chromatography.

[0421] In the case of selecting any method, it is preferred to prepare the composition while minimizing the presence of oxygen and water.

[0422] For example, the dissolved oxygen concentration in the polymerization solution in solution polymerization is preferably less than 300 ppm in the polymerization step, and in a production method using an extruder or the like, the oxygen concentration in the extruder is preferably less than 1% by volume, more preferably less than 0.8% by volume. The water content of the methacrylic resin is preferably adjusted to 1000 ppm by mass or less, more preferably 500 ppm by mass or less.

[0423] As long as the content is within these ranges, it is relatively easy to prepare a composition satisfying the requirements of the present invention, which is advantageous.

[0424] [Method for manufacturing resin prism for polarization beam splitter]

[0425] The resin prism for polarization beam splitter of this embodiment is formed by molding the above resin composition. As a manufacturing method of the resin prism for polarization beam splitter of this embodiment, a molding method such as injection molding, compression molding, and extrusion molding can be used. Among them, injection molding is preferred from the viewpoint of productivity.

[0426] In general, the injection molding method consists of the following steps: (1) an injection step, in which the resin is melted and the molten resin is filled into the cavity of a temperature-controlled mold; (2) a pressure holding step, in which pressure is applied to the cavity until the gate is sealed, and an amount of resin equivalent to the molten resin filled in the injection step contacts the mold and cools and shrinks is injected; (3) a cooling step, in which the pressure holding is released and the molded product is held until the resin is cooled; and (4) a step of opening the mold and taking out the cooled molded product.

[0427] At this time, the molding temperature can be in the range of Tg+100°C to Tg+160°C, preferably in the range of Tg+110°C to Tg+150°C, based on the glass transition temperature (Tg) of the resin composition. Here, the molding temperature refers to the controlled temperature of the belt heater wound on the injection nozzle. The higher the molding temperature, the lower the phase difference of the resin prism can be obtained, but the coloring caused by thermal degradation when the prism is retained in the molding machine is promoted at high temperature, so it is necessary to select the molding temperature appropriately.

[0428] The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-20°C, based on the glass transition temperature (Tg) of the resin composition.

[0429] The injection speed can be appropriately selected according to the thickness and size of the resin prism to be obtained, and can be appropriately selected within the range of 10 to 1000 mm / sec, for example.

[0430] The pressure for holding the pressure can be appropriately selected according to the shape of the resin prism to be obtained, and can be appropriately selected within the range of 30 to 120 MPa, for example.

[0431] Here, the pressure for holding pressure refers to the pressure maintained by the screw for further sending out the molten resin from the gate after the molten resin is filled.

[0432] In addition, in order to relieve the residual stress caused by injection molding and reduce the phase difference of the resin prism, an annealing process may be performed. The temperature during annealing is preferably in the range of Tg-50°C to Tg, and more preferably in the range of Tg-30°C to Tg-10°C, based on the glass transition temperature (Tg) of the resin composition.

[0433] The surface of the resin prism for polarization beam splitter of this embodiment may be further subjected to surface functionalization treatments such as hard coating treatment, anti-reflection treatment, transparent conductive treatment, electromagnetic wave shielding treatment, gas barrier treatment, etc. The thickness of these functional layers is not particularly limited, but is generally in the range of 0.01 to 10 μm.

[0434] As a hard coating layer imparted on its surface, for example, a coating liquid prepared by dissolving or dispersing a silicone-based curable resin, a curable resin containing organic polymer composite inorganic particles, an acrylate such as urethane acrylate, epoxy acrylate, multifunctional acrylate, and a photopolymerization initiator in an organic solvent is applied to a film or plate obtained from the resin composition of this embodiment using a conventionally known coating method, dried, and photocured to form a hard coating layer.

[0435] In order to improve the adhesiveness, for example, an easy-adhesion layer containing inorganic fine particles, a primer layer, an anchor layer, etc. may be provided before applying the hard coating layer, and then the hard coating layer may be formed.

[0436] As the anti-glare layer provided on the surface, fine particles of silica, melamine resin, acrylate resin, etc. are ink-formed, applied on other functional layers by a conventionally known coating method, and thermally or photocured to form the anti-glare layer.

[0437] Examples of the antireflection layer imparted to the surface include an antireflection layer composed of a thin film of an inorganic substance such as a metal oxide, fluoride, silicide, boride, nitride, sulfide, etc.; an antireflection layer composed of a single layer or multiple layers of resins having different refractive indices such as an acrylate resin or a fluororesin, etc.; and an antireflection layer formed by stacking thin layers of composite particles containing inorganic compounds and organic compounds.

[0438] [Example]

[0439] The present invention will be described in detail below with reference to Examples and Comparative Examples. It should be noted that the present invention is not limited to the following Examples.

[0440] <1. Determination of the amount of 2-cyclohexylamino-N-cyclohexylsuccinimide in N-cyclohexylmaleimide>

[0441] N-cyclohexylmaleimide or N-cyclohexylmaleimide / m-xylene solution was collected and weighed to prepare a 25% by mass m-xylene solution of N-cyclohexylmaleimide, isopropyl benzoate was added as an internal standard substance, and the result was determined by measuring using a gas chromatograph (manufactured by Shimadzu Corporation, GC-2014) under the following conditions.

[0442] Detector: FID.

[0443] Chromatographic column used: HP-5ms.

[0444] Measurement conditions: After holding at 80°C for 5 minutes, the temperature was increased to 300°C at a temperature increase rate of 10°C / min, and then held for 5 minutes.

[0445] <2. Determination of the amount of 2-anilino-N-phenylsuccinimide in N-phenylmaleimide>

[0446] N-phenylmaleimide or N-phenylmaleimide / m-xylene solution was collected and weighed to prepare a 10% by mass m-xylene solution of N-phenylmaleimide, isopropyl benzoate was added as an internal standard substance, and the solution was determined by measurement using a liquid chromatograph (manufactured by Waters Corporation, UPLC H-class) under the following conditions.

[0447] Detector: PDA (detection wavelength: 210nm~300nm).

[0448] Chromatographic column used: ACQUITY UPLC HSS T3.

[0449] Column temperature: 40°C.

[0450] Mobile phase: 50% acetonitrile in water containing 0.1% formic acid.

[0451] Flow rate: 0.4mL / min.

[0452] <3. Determination of the residual amount of N-substituted maleimide monomer>

[0453] A portion of the analysis object (polymer solution or methacrylic resin particles after polymerization) was collected and weighed, and the sample was dissolved in chloroform to prepare a 5 mass % solution. n-decane was added as an internal standard substance, and the solution was measured and determined under the following conditions using a gas chromatograph (manufactured by Shimadzu Corporation, GC-2010).

[0454] Detector: FID.

[0455] Chromatographic column used: ZB-1.

[0456] Measurement conditions: After holding at 45°C for 5 minutes, the temperature was increased to 300°C at a rate of 20°C / min, and then held for 15 minutes.

[0457] <4. Analysis of structural units>

[0458] Unless otherwise specified, each structural unit in the methacrylic resin produced in the production examples and comparative examples described below is represented by 1 H-NMR determination and 13 The structural units of the methacrylic resin and the methacrylic resin composition were identified by C-NMR measurement, and the amounts thereof were calculated. 1 H-NMR determination and 13 The measurement conditions of C-NMR measurement are as follows.

[0459] · Measurement equipment: JNM-ECZ400S manufactured by JEOL Ltd.

[0460] ·Measurement solvent: CDCl 3 or 6 -DMSO.

[0461] ·Measurement temperature: 40℃.

[0462] <5. Molecular weight and molecular weight distribution>

[0463] The weight average molecular weight (Mw), number average molecular weight (Mn), and Z average molecular weight (Mz) of the methacrylic resin compositions produced in the Production Examples and Comparative Production Examples described below were measured using the following apparatuses and conditions.

[0464] · Measurement apparatus: Gel permeation chromatograph (HLC-8320GPC) manufactured by Tosoh Corporation.

[0465] ·Measurement conditions:

[0466] Chromatographic columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-Ms, and one TSKgel SuperH2500 are connected in series.

[0467] Column temperature: 40°C.

[0468] The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 0.1 g / L of 2,6-di-tert-butyl-4-methylphenol (BHT) was added as an internal standard.

[0469] Detector: RI (differential refractometer) detector.

[0470] Detection sensitivity: 3.0mV / min.

[0471] Sample: 20 mL of tetrahydrofuran solution of 0.02 g of a methacrylic resin composition.

[0472] Injection volume: 10 μL.

[0473] Standard samples for calibration curves: The following ten types of polymethyl methacrylates having known monodisperse weight peak molecular weights and different molecular weights (manufactured by Polymer Laboratories; PMMA Calibration Kit MM-10) were used.

[0474] Weight peak molecular weight (Mp)

[0475] Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850

[0476] Under the above-mentioned conditions, the RI detection intensity relative to the elution time of the methacrylic resin composition was measured.

[0477] Based on each calibration curve obtained by measuring the calibration curve standard sample, the weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) of the methacrylic resin composition are determined, and the molecular weight distribution (Mw / Mn) and (Mz / Mw) are determined using these values.

[0478] <6. Phase difference of resin prism>

[0479] The hypotenuses of a pair of right-angle prisms obtained from the examples and comparative examples are joined together to form a cube, and a birefringence evaluation system PA-200-L manufactured by Photonic Lattice, Inc. (Photonic Lattice, Inc.) is used to measure the surface distribution of the phase difference of the prism by allowing light to pass through the incident and exit surfaces at a wavelength of 520 nm. The area within the prism is designated, and the average value (nm) of the absolute value of the phase difference is calculated.

[0480] <7. Content of fluorescent material in resin prism>

[0481] The resin prisms obtained in the examples and comparative examples were finely cut and weighed into a glass sample bottle, and chloroform was added. The solution was shaken at a speed of 800 times per minute for 30 minutes using an oscillator to prepare a 2.0% by mass chloroform solution of the resin prism. The fluorescence intensity was measured using a fluorescence spectrophotometer (Fluorolog 3-22 manufactured by Horiba Jobin Yvon).

[0482] Regarding the measurement conditions, a xenon lamp was used as the light source, a PMT was used as the detector, the excitation wavelength was 436 nm, the slit width was set to 2 nm on both the excitation side and the observation side, the time constant was 0.2 s, the measurement mode was Sc / Rc in which the luminescence intensity was standardized by the excitation light intensity at each wavelength, and a quartz cuvette with an optical path length of 1 cm was used for 90° observation for measurement.

[0483] The obtained fluorescence intensity at a wavelength of 530 nm was normalized using the fluorescence intensity of a fluorescein / ethanol solution. Specifically, the method is as follows.

[0484] Calculate the relative humidity of ethanol and 5×10 -8 mol / L and 1×10 -6 The fluorescence intensity at a wavelength of 530 nm when the fluorescein / ethanol solution of mol / L was spectroscopically analyzed at an excitation wavelength of 436 nm was subtracted from the blank of ethanol to prepare a concentration-intensity conversion formula. The fluorescence emission spectrum of chloroform was measured, and the emission intensity of chloroform at a wavelength of 530 nm was subtracted from the emission intensity of chloroform at a wavelength of 530 nm of the chloroform solution of a 2.0 mass % resin prism, and the concentration was converted using the previously obtained concentration-intensity conversion formula of the fluorescein / ethanol solution to obtain the content (mol / L) of the fluorescent substance.

[0485] <8. Glass transition temperature of resin prism>

[0486] The glass transition temperature (Tg) (° C.) of the resin prism was measured in accordance with JIS-K7121.

[0487] First, as test pieces, approximately 10 mg of each of the test pieces were cut out at four points (four places) from a resin prism that had been conditioned (left at 23° C. for one week) under a standard state (23° C., 50% RH).

[0488] Next, a differential scanning calorimeter (Diamond DSC manufactured by PerkinElmer Japan Co., Ltd.) was used under the condition of a nitrogen flow rate of 25 mL / min. Here, the temperature was raised from room temperature (23°C) to 200°C at 10°C / min (primary heating), and maintained at 200°C for 5 minutes to completely melt the sample. Then, the temperature was lowered from 200°C to 40°C at 10°C / min, and maintained at 40°C for 5 minutes. The temperature was further raised again under the above heating conditions (secondary heating). In the DSC curve drawn during this period, the intersection of the step-shaped change portion curve at the time of the secondary heating and the straight line at an equal distance from each baseline extension line in the vertical axis direction (midpoint glass transition temperature) was measured as the glass transition temperature (Tg) (°C). Four points were measured for each sample, and the arithmetic mean (rounded off below the decimal point) of the four points was taken as the measured value.

[0489] <9. Photoelastic coefficient of resin prism>

[0490] The resin prisms obtained in Examples and Comparative Examples were finely cut and then formed into pressed films using a vacuum compression molding machine to prepare measurement samples.

[0491] As specific sample preparation conditions, a vacuum compression molding machine (manufactured by Shinto Metal Industry, SFV-30 model) was used. After preheating at 260°C and reduced pressure (about 10 kPa) for 10 minutes, the resin prism was compressed at 260°C and about 10 MPa for 5 minutes. After the reduced pressure and compression pressure were released, the prism was transferred to a cooling compression molding machine for cooling and solidification. The obtained pressed film was aged in a constant temperature and humidity room adjusted to 23°C and 60% humidity for more than 24 hours, and on this basis, a test piece for measurement (thickness of about 150 μm, width of 6 mm) was cut out.

[0492] The photoelastic coefficient C was measured using a birefringence measuring apparatus described in detail in Polymer Engineering and Science (1999, 39, 2349-2357). R (Pa -1 ).

[0493] The film-like test piece was placed in a film stretching device (manufactured by Imoto Seisakusho) similarly set in a constant temperature and humidity chamber so that the distance between the chucks was 50 mm. Next, the device was placed so that the laser beam path of the birefringence measuring device (manufactured by Otsuka Electronics, RETS-100) was located at the center of the film, and the birefringence of the test piece was measured while applying tensile stress at a deformation speed of 50% / min (distance between the chucks: 50 mm, chuck moving speed: 5 mm / min).

[0494] The birefringence (Δn) and tensile stress (σ R ), the slope of the straight line was obtained by least squares approximation, and the photoelastic coefficient (C R )(Pa -1 ). In the calculation, the tensile stress is used to be 2.5MPa≤σ R Data between ≤10MPa.

[0495] C R =Δn / σ R

[0496] Here, the birefringence (Δn) is a value as shown below.

[0497] Δn=nx-ny

[0498] (nx: refractive index in the stretching direction, ny: refractive index in the direction perpendicular to the stretching direction in the plane)

[0499] <10. Light transmittance of resin prism>

[0500] For the resin prisms obtained from the examples and comparative examples, the hypotenuses of a pair of right-angle prisms were combined to form a cube, and light was transmitted through the incident surface and the emitting surface. The transmittance (%) was measured every 5 nm in the range of wavelength 380 to 780 nm with a D65 light source and a 10° field of view. The ratio (T450 / T680) of the transmittance (T450) at a wavelength of 450 nm to the transmittance (T680) at a wavelength of 680 nm was obtained using the measured values.

[0501] <11. Image clarity>

[0502] Using the resin prisms obtained in the examples and comparative examples, a reflective polarizing film was sandwiched and bonded between the hypotenuses of a pair of right-angle prisms to produce a cube-shaped polarizing beam splitter. Figure 1 The evaluation system shown.

[0503] The evaluation system is formed by combining a blue LED (peak wavelength: about 465nm) 1, a collimating lens 2, a polarizing beam splitter 3, a reflective liquid crystal panel (LCOS: Liquid Crystal On Silicon) 4, a projection lens 5, and a screen 6. The polarizing beam splitter 3 is made by sandwiching and bonding a reflective polarizing film 33 between the hypotenuses of a pair of resin right-angle prisms 31 and 32 obtained in the embodiment and the comparative example. After the light from the blue LED 1 becomes parallel light through the collimating lens 2, it enters the polarizing beam splitter 3, passes through the resin prism 31, and is split into P polarized light and S polarized light through the reflective polarizing film 33. The S polarized light is folded back 90° by the reflective polarizing film 33 and enters the reflective liquid crystal panel 4. In the reflective liquid crystal panel 4, the incident S-polarized light is converted into P-polarized light and reflected in the pixel of the on signal, and is reflected in the state of S-polarized light in the pixel of the off signal, and is incident on the resin prism 31 and reaches the reflective polarizing film 33. The P-polarized light passes through the reflective polarizing film 33, passes through the resin prism 32, is magnified by the projection lens 5, and is projected onto the screen 6.

[0504] The still image displayed on the screen 6 was observed by the above-mentioned simulation device, and the clarity of the image was evaluated according to the following evaluation criteria.

[0505] [Evaluation criteria]

[0506] Image clarity

[0507] ○: No bleeding or blurring was observed in the image.

[0508] △: The image becomes slightly unclear due to bleeding and blurring, but the image being projected can be recognized.

[0509] ×: The image became unclear due to bleeding and blurring, so it was impossible to recognize what was being projected.

[0510] Color reproduction

[0511] ○: Blue is reproduced clearly.

[0512] ×: The reproduction degree of blue is poor.

[0513] [raw material]

[0514] The raw materials used in the following Examples and Comparative Examples are as follows.

[0515] [[monomer]]

[0516] ·Methyl methacrylate (MMA): manufactured by Asahi Kasei Co., Ltd.

[0517] N-Cyclohexylmaleimide (chMI): manufactured by Nippon Shokubai Co., Ltd.

[0518] (The mass ratio of 2-cyclohexylamino-N-cyclohexylsuccinimide (CCSI) to the mass of chMI is 80 mass ppm)

[0519] N-Phenylmaleimide (phMI): manufactured by Nippon Shokubai Co., Ltd.

[0520] (The mass ratio of 2-anilino-N-phenylsuccinimide (APSI) to the mass of phMI is 60 mass ppm)

[0521] -Pretreatment of N-substituted maleimide (chMI, phMI) (water washing and dehydration steps)-

[0522] The N-cyclohexylmaleimide (chMI) and N-phenylmaleimide (phMI) are subjected to the following water washing and dehydration steps to remove 2-amino-N-substituted succinimide (CCSI, APSI) and water.

[0523] --Washing and dehydration of N-cyclohexylmaleimide (chMI)--

[0524] ---Reducing CCSI in N-cyclohexylmaleimide to 5 mass ppm or less---

[0525] 250.0 kg of chMI and 750.0 kg of m-xylene (hereinafter referred to as "mXy") were weighed and added to a 2.0 m3 / 4-gallon stirrer equipped with a jacketed temperature control device and three swept blades as stirring blades. 3 Steam was blown into the jacket of a glass-lined reactor to raise the temperature of the solution in the reactor to 56°C, and the solution was stirred to obtain an organic layer. Next, 350.0 kg of 2% by mass sulfuric acid water was weighed and added to the reactor, and the solution temperature was maintained at 56°C and stirred at 100 rpm for 10 minutes. Stirring was stopped, and the solution was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0526] The same operation was repeated two more times, and the operation of washing the organic layer with sulfuric acid water was performed three times in total. The amount of CCSI in the organic layer was quantified by gas chromatography, and the result was 4.9 mass ppm relative to chMI in the organic layer.

[0527] Thereafter, 350.0 kg of ion exchange water was added to the reactor, and the solution temperature was maintained at 55° C., and stirred at 100 rpm for 10 minutes. Stirring was stopped, and the mixture was allowed to stand for 20 minutes, and the water layer was extracted into a drum tank.

[0528] The same operation was repeated once more, and the operation of washing the organic layer with ion exchange water was performed twice in total. The amount of CCSI in the organic layer was quantified by gas chromatography, and the result was 4.6 mass ppm relative to the chMI in the organic layer.

[0529] Next, the solution temperature was maintained at 50°C, and the pressure in the reactor was gradually reduced while stirring at 100 rpm to a pressure of 5 kPa. Thereafter, the solution temperature was raised to 60°C, and an azeotropic dehydration operation was performed. 131.6 kg of the water / mXy mixed solution was distilled off, and the water concentration in the organic layer was quantified by a Karl Fischer titrator, and the result was 102 mass ppm relative to the mass of the organic layer.

[0530] mXy for concentration adjustment was added to the organic layer to obtain 1034.3 kg of an organic layer having a chMI of 24.0 mass %, a water concentration of 191 mass ppm, and a CCSI of 4.6 mass ppm relative to the mass of chMI.

[0531] ---Reducing CCSI in N-cyclohexylmaleimide to less than 1 mass ppm---

[0532] 80.0 kg of chMI and 240.0 kg of mXy were weighed and added to a 0.50 m3 full zone mixer made by Kobelco Environmental Solutions, which was equipped with a jacket-based temperature control device and a stirring blade. 3 Steam was blown into the jacket of a glass-lined reactor to raise the temperature of the solution in the reactor to 55°C, and the solution was stirred to obtain an organic layer. Next, 112.0 kg of 2% by mass sulfuric acid water was weighed and added to the reactor, and the solution temperature was maintained at 55°C and stirred at 100 rpm for 30 minutes. Stirring was stopped, and the solution was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0533] The same operation was repeated three more times, and the operation of washing the organic layer with sulfuric acid water was performed a total of four times. The amount of CCSI in the organic layer was quantified by gas chromatography, and the result was 0.57 mass ppm relative to the chMI in the organic layer.

[0534] Thereafter, 112.0 kg of ion exchange water was added to the reactor, and the solution temperature was maintained at 55° C., and stirred at 100 rpm for 30 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0535] The solution temperature was maintained at 50°C, and the pressure in the reactor was gradually reduced while stirring at 100 rpm to 5 kPa. Thereafter, the solution temperature was raised to 60°C for azeotropic dehydration. 54 kg of the water / mXy mixed solution was distilled off, and the water concentration in the organic layer was quantified by a Karl Fischer titrator, and the result was 46 mass ppm relative to the mass of the organic layer.

[0536] mXy for concentration adjustment was added to the organic layer to obtain 384.0 kg of an organic layer having a chMI of 20.3 mass %, a water concentration of 125 mass ppm, and a CCSI of 0.60 mass ppm relative to the mass of chMI.

[0537] --Washing and dehydration of N-phenylmaleimide (phMI)--

[0538] ---Reducing APSI in N-phenylmaleimide to less than 5 mass ppm---

[0539] 150.0 kg of phMI and 720.0 kg of mXy were weighed and added to a 2.0 m 3 Steam was blown into the jacket of a glass-lined reactor to raise the temperature of the solution in the reactor to 55°C, and the mixture was stirred to obtain an organic layer. Next, 336.0 kg of 7% by mass sodium bicarbonate water was measured and added to the reactor, and the solution temperature was maintained at 55°C and stirred at 100 rpm for 10 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0540] Next, 336.0 kg of ion exchange water was added to the reactor, and the solution temperature was maintained at 55° C., and stirred at 100 rpm for 10 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0541] Thereafter, 336.0 kg of 2 mass % sulfuric acid water was measured and added to the reactor, and the solution temperature was maintained at 55° C. and stirred at 100 rpm for 10 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0542] In the same manner as above, the washing operation with ion exchange water was further performed twice.

[0543] The amount of APSI in the organic layer was quantified by liquid chromatography and found to be 3.6 ppm by mass relative to phMI in the organic layer.

[0544] Next, the solution temperature was maintained at 50°C, and the pressure in the reactor was gradually reduced while stirring at 100 rpm to 5 kPa. Thereafter, the solution temperature was raised to 55°C, and an azeotropic dehydration operation was performed. 190 kg of the water / mXy mixed solution was distilled off, and the water concentration in the organic layer was quantitatively determined by a Karl Fischer titrator, and the result was 47 mass ppm relative to the mass of the organic layer.

[0545] mXy for concentration adjustment was added to the organic layer to obtain 1340.7 kg of an organic layer having a phMI of 10.8 mass %, a water concentration of 170 mass ppm, and an APSI of 3.4 mass ppm relative to the mass of phMI.

[0546] ---Reducing APSI in N-phenylmaleimide to less than 1 mass ppm---

[0547] 50.0 kg of phMI and 240.0 kg of mXy were weighed and added to a 0.50 m full zone mixer manufactured by Kobelco Environmental Solutions, which was equipped with a jacketed temperature control device and a stirring blade. 3 The glass-lined reactor was blown with steam into the jacket to raise the temperature of the solution in the reactor to 55°C, and stirred to obtain an organic layer. Next, 112.0 kg of 7% by mass sodium bicarbonate water was measured and added to the reactor, the solution temperature was maintained at 55°C, and stirred at 100 rpm for 15 minutes. Stirring was stopped, the solution was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank. The same operation was repeated once more, and the operation of washing the organic layer with sodium bicarbonate water was performed twice in total.

[0548] Next, 112.0 kg of ion exchange water was added to the reactor, and the solution temperature was maintained at 55° C., and stirred at 100 rpm for 30 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank.

[0549] Thereafter, 112.0 kg of 2 mass % sulfuric acid water was measured and added to the reactor, and the solution temperature was maintained at 55° C. and stirred at 100 rpm for 30 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes, and the water layer was extracted into a drum tank. The same operation was further repeated twice, and the operation of washing the organic layer with sulfuric acid water was performed a total of three times.

[0550] In the same manner as above, the washing operation with ion exchange water was further performed twice.

[0551] The amount of APSI in the organic layer was quantified by liquid chromatography and found to be 0.37 mass ppm relative to phMI in the organic layer.

[0552] The solution temperature was maintained at 50°C, and the pressure in the reactor was gradually reduced while stirring at 100 rpm to a pressure of 5 kPa. Thereafter, the solution temperature was raised to 55°C, and an azeotropic dehydration operation was performed. 72 kg of the water / mXy mixed solution was distilled off, and the water concentration in the organic layer was quantified by a Karl Fischer titrator, and the result was 60 mass ppm relative to the mass of the organic layer.

[0553] mXy for concentration adjustment was added to the organic layer to obtain 432.8 kg of an organic layer having a phMI of 10.3 mass %, a water concentration of 180 mass ppm, and an APSI of 0.42 mass ppm relative to the mass of phMI.

[0554] [[Polymerization initiator]]

[0555] · 1,1-Di(tert-butylperoxy)cyclohexane: “PERHEXA C” manufactured by NOF Corporation.

[0556] [[Chain transfer agent]]

[0557] ·N-octylmercaptan: manufactured by Kao Corporation.

[0558] [[Hindered phenol antioxidants]]

[0559] · Irganox 1010: manufactured by BASF.

[0560] [[Phosphorus antioxidants]]

[0561] · Irgafos 168 (melting point 180-190° C.): manufactured by BASF.

[0562] [Methacrylic resin composition]

[0563] [Manufacturing Example 1]

[0564] 374.8 kg of mXy solution with a phMI content of 10.3% by mass (APSI with respect to the mass of phMI is 0.42 mass ppm) after washing and dehydration and 323.6 kg of mXy solution with a chMI content of 20.3% by mass (CCSI with respect to the mass of chMI is 0.60 mass ppm) after washing and dehydration were weighed and added to a 1.25 m3 / s stirring vessel equipped with a jacketed temperature control device and a stirring blade. 3The reactor was stirred at a solution temperature of 60°C and a pressure of 5 kPa in the reactor while distilling off 160.8 kg of mXy under reduced pressure. Next, the reactor was returned to normal pressure and 16.7 kg of mXy was added to prepare a mixed solution of 38.6 kg of phMI, 65.7 kg of chMI, and 450.0 kg of mXy. 445.7 kg of MMA and 0.413 kg of n-octyl mercaptan as a chain transfer agent were weighed, added, and stirred to obtain a monomer mixed solution.

[0565] The liquid content in the reactor was bubbling with nitrogen at a rate of 30 L / min for 1 hour to remove dissolved oxygen.

[0566] Thereafter, steam was blown into the jacket to raise the temperature of the solution in the reactor to 125° C., and a polymerization initiator solution of 0.23 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 2.77 kg of mXy was added at a rate of 0.5 kg / hour while stirring at 50 rpm to start polymerization. The addition was stopped 6 hours after the start of the polymerization.

[0567] During the polymerization, the temperature of the solution in the reactor was controlled at 125±2° C. by temperature regulation using a jacket.

[0568] After 8 hours had passed from the start of the polymerization, a polymerization solution containing a methacrylic resin having a ring structure in its main chain was obtained.

[0569] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 1340 mass ppm of phMI and 4390 mass ppm of chMI were contained.

[0570] To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added under stirring based on 100 mass % of the polymer contained in the solution.

[0571] The polymerization solution containing the antioxidant was filtered by passing it through a filter having a filtration accuracy of 2 μm and composed of metal fibers made of SUS316L.

[0572] In order to recover the polymer from the polymerization solution, a plate heat exchanger having a plate slit flow path and a heat medium flow path and an inner volume of about 0.3m 3 The devolatilization device is composed of a reduced pressure container (hereinafter referred to as a devolatilization tank) with a SUS heating medium jacket.

[0573] The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed on the upper part of the reduced pressure container at a rate of 30 liters / hour, and after being heated to 260°C, it was supplied to a devolatilization tank heated and decompressed to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization. The shear rate in the devolatilization device was calculated based on the device shape and operating conditions, and it was 5.3s -1 .

[0574] The devolatilized polymer was pressurized from the lower portion of the devolatilization tank by a gear pump, extruded from a strand die, water-cooled, and pelletized to obtain a methacrylic resin composition A.

[0575] The composition of the methacrylic resin composition A was confirmed to contain 81.2 mass %, 7.1 mass % and 11.7 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 148,000, Mw / Mn was 2.12, Mz / Mw was 1.63, and the glass transition temperature was 133°C.

[0576] [Manufacturing Example 2]

[0577] 352.4 kg of mXy solution with 10.3 mass % phMI (APSI with respect to the mass of phMI is 0.42 mass ppm) after washing and dehydration and 310.3 kg of mXy solution with 20.3 mass % chMI (CCSI with respect to the mass of chMI is 0.60 mass ppm) after washing and dehydration were weighed and added to a 1.25 m3 / s stirring vessel equipped with a jacketed temperature control device and a stirring blade. 3 The reactor was stirred under reduced pressure while removing 335.4 kg of mXy at a solution temperature of 60°C and a pressure of 5 kPa in the reactor. Next, the reactor was returned to normal pressure and 8.9 kg of mXy was added to prepare a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octyl mercaptan as a chain transfer agent were weighed, added, and stirred to obtain a monomer mixed solution.

[0578] Next, 123.1 kg of mXy was measured and added to Tank 1.

[0579] Furthermore, 110.0 kg of MMA and 90.0 kg of mXy were weighed and stirred in a tank 2 to prepare a monomer solution for supplementary addition.

[0580] The liquid content in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes in each of tank 1 and tank 2 to remove dissolved oxygen.

[0581] Thereafter, steam was blown into the jacket to raise the temperature of the solution in the reactor to 128° C., and a polymerization initiator solution of 0.37 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 3.005 kg of mXy was added at a rate of 1 kg / hour while stirring at 50 rpm to start polymerization. 0.5 hour after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour, and mXy was added from tank 1 at 35.2 kg / hour for 3.5 hours.

[0582] During the polymerization, the temperature of the solution in the reactor was controlled at 128±2° C. by temperature regulation using a jacket.

[0583] Next, 4 hours after the start of the polymerization, the addition rate of the initiator solution was changed to 0.75 kg / hour, and at the same time, the monomer solution containing MMA was added from the tank 2 at a rate of 100.0 kg / hour for 2 hours.

[0584] Furthermore, the addition rate of the initiator solution was reduced to 0.5 kg / hour 6 hours after the start of polymerization, and the addition was stopped 7 hours after the start of polymerization. The polymerization was further continued for 1 hour to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in the main chain.

[0585] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 220 mass ppm of phMI and 1070 mass ppm of chMI were contained.

[0586] To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added under stirring based on 100 mass % of the polymer contained in the solution.

[0587] The polymerization solution containing the antioxidant was filtered by passing through a filter having a filtration accuracy of 2 μm and composed of metal fibers made of SUS316L.

[0588] In order to recover the polymer from the polymerization solution, a plate heat exchanger having a plate slit flow path and a heat medium flow path and a 1.5-meter-high heat exchanger having an internal volume of about 0.3 m 3 A devolatilization device is provided which is composed of a decompression container (hereinafter referred to as a devolatilization tank) with a SUS heating medium jacket, and the devolatilization device does not have a rotating part.

[0589] The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed on the upper part of the reduced pressure container at a rate of 30 liters / hour, and after being heated to 260°C, it was supplied to a devolatilization tank heated and decompressed to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization. The shear rate in the devolatilization device was calculated based on the device shape and operating conditions, and it was 5.3s -1 .

[0590] The devolatilized polymer was pressurized from the lower portion of the devolatilization tank by a gear pump, extruded from a strand die, water-cooled, and pelletized to obtain a methacrylic resin composition B.

[0591] The composition of the methacrylic resin composition B was confirmed to contain 80.9 mass %, 7.0 mass % and 12.1 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 142,000, Mw / Mn was 2.32, Mz / Mw was 1.75, and the glass transition temperature was 134°C.

[0592] [Manufacturing Example 3]

[0593] A methacrylic resin composition C was obtained in the same manner as in Manufacturing Example 2 except that a 10.8% by mass mXy solution (APSI with respect to the mass of phMI was 3.4% by mass ppm) was used as the phMI that had undergone the water washing step and the dehydration step, and a 24.0% by mass mXy solution (CCSI with respect to the mass of chMI was 4.6% by mass ppm) was used as the chMI that had undergone the water washing step and the dehydration step, and the composition of the mixed solution prepared in the reactor was the same as that in Manufacturing Example 2.

[0594] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 210 mass ppm of phMI and 1090 mass ppm of chMI were contained.

[0595] The composition of the methacrylic resin composition C was confirmed to contain 80.8 mass %, 7.1 mass % and 12.1 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 141,000, Mw / Mn was 2.31, Mz / Mw was 1.75, and the glass transition temperature was 134°C.

[0596] [Manufacturing Example 4]

[0597] In a reactor equipped with a jacketed temperature control device and a stirring blade, 40 parts by mass of MMA and 60 parts by mass of mXy, and 0.08 parts by mass of n-octyl mercaptan as a chain transfer agent were placed, and nitrogen bubbling was performed for 1 hour to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the temperature of the solution in the reactor to 120°C, and a polymerization initiator solution of 0.02 parts by mass of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 0.10 parts by mass of mXy was added at a constant rate for 5 hours while stirring at 50 rpm, thereby polymerizing, and further aging at 120°C for 3 hours. The polymerization was terminated 8 hours after the start of the polymerization to obtain a PMMA mXy solution. After the polymerization was completed, the liquid temperature was lowered to 50°C.

[0598] Next, a mixed liquid consisting of 12 parts by mass of monomethylamine and 12 parts by mass of methanol was added dropwise to the reactor at room temperature, and the liquid temperature was raised to 170° C. and stirred under pressure for 1 hour to carry out a glutarimide cyclization reaction. The liquid temperature was lowered to 120° C., and the pressure in the reactor was reduced to distill off unreacted monomethylamine and methanol and a portion of mXy, thereby obtaining an mXy solution containing about 50% by mass of a glutarimide cyclized methacrylic acid-based polymer.

[0599] To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added under stirring based on 100 mass % of the polymer contained in the solution.

[0600] The polymerization solution containing the antioxidant was filtered by passing through a filter having a filtration accuracy of 2 μm and composed of metal fibers made of SUS316L.

[0601] In order to recover the polymer from the polymerization solution, a plate heat exchanger having a plate slit flow path and a heat medium flow path and a 1.5-meter-high heat exchanger having an internal volume of about 0.3 m 3 A devolatilization device is provided which is composed of a decompression container (hereinafter referred to as a devolatilization tank) with a SUS heating medium jacket, and the devolatilization device does not have a rotating part.

[0602] The solution containing the polymer obtained by polymerization was supplied to a heat exchanger installed on the upper part of the reduced pressure container at a rate of 30 liters / hour, and after being heated to 260°C, it was supplied to a devolatilization tank heated and decompressed to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization. The shear rate in the devolatilization device was calculated based on the device shape and operating conditions, and it was 5.3s -1 .

[0603] The devolatilized polymer was pressurized from the lower portion of the devolatilization tank by a gear pump, extruded from a strand die, water-cooled, and pelletized to obtain a methacrylic resin composition D.

[0604] The composition of the obtained methacrylic resin composition D was confirmed to have an imidization rate of 3.2%, a glutarimide structural unit content of 5.1% by mass, a weight average molecular weight Mw of 93,000, Mw / Mn of 1.79, Mz / Mw of 1.51, and a glass transition temperature of 122°C.

[0605] [Manufacturing Example 5]

[0606] A methacrylic resin composition E was obtained in the same manner as in Production Example 2 except that the amounts of the monomers in the solution prepared in the reactor were 39.3 kg of phMI, 46.5 kg of chMI, and 354.2 kg of MMA.

[0607] The composition of the methacrylic resin composition E was confirmed to contain 83.2 mass %, 7.6 mass % and 9.2 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 143,000, Mw / Mn was 2.35, Mz / Mw was 1.81, and the glass transition temperature was 132°C.

[0608] [Comparative Manufacturing Example 1]

[0609] 352.4 kg of mXy solution with 10.3 mass % phMI (APSI with respect to the mass of phMI is 0.42 mass ppm) after washing and dehydration and 310.3 kg of mXy solution with 20.3 mass % chMI (CCSI with respect to the mass of chMI is 0.60 mass ppm) after washing and dehydration were weighed and added to a 1.25 m3 / s stirring vessel equipped with a jacketed temperature control device and a stirring blade. 3 The reactor was stirred under reduced pressure while removing 335.4 kg of mXy at a solution temperature of 60°C and a pressure of 5 kPa in the reactor. Next, the reactor was returned to normal pressure and 8.9 kg of mXy was added to prepare a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octyl mercaptan as a chain transfer agent were weighed, added, and stirred to obtain a monomer mixed solution.

[0610] Next, 123.1 kg of mXy was measured and added to Tank 1.

[0611] Furthermore, 110.0 kg of MMA and 90.0 kg of mXy were weighed and stirred in a tank 2 to prepare a monomer solution for supplementary addition.

[0612] The liquid content in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and nitrogen was bubbled with nitrogen at a rate of 10 L / min for 30 minutes in each of tank 1 and tank 2 to remove dissolved oxygen.

[0613] Thereafter, steam was blown into the jacket to raise the temperature of the solution in the reactor to 128° C., and a polymerization initiator solution of 0.37 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 3.005 kg of mXy was added at a rate of 1 kg / hour while stirring at 50 rpm to start polymerization. 0.5 hour after the start of polymerization, the addition rate of the initiator solution was reduced to 0.25 kg / hour, and mXy was added from tank 1 at 35.2 kg / hour for 3.5 hours.

[0614] During the polymerization, the temperature of the solution in the reactor was controlled at 128±2° C. by temperature regulation using a jacket.

[0615] Next, 4 hours after the start of the polymerization, the addition rate of the initiator solution was changed to 0.75 kg / hour, and at the same time, the monomer solution containing MMA was added from the tank 2 at a rate of 100.0 kg / hour for 2 hours.

[0616] Furthermore, the addition rate of the initiator solution was reduced to 0.5 kg / hour 6 hours after the start of polymerization, and the addition was stopped 7 hours after the start of polymerization. The polymerization was further continued for 1 hour to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in the main chain.

[0617] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 220 mass ppm of phMI and 1070 mass ppm of chMI were contained.

[0618] To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added under stirring based on 100 mass % of the polymer contained in the solution.

[0619] The polymerization solution containing the antioxidant was filtered by passing through a filter having a filtration accuracy of 2 μm and composed of metal fibers made of SUS316L.

[0620] Next, the obtained polymer solution is introduced into a twin-screw extruder equipped with a plurality of vent holes for devolatilization, thereby devolatilization is performed. In the twin-screw extruder, the obtained polymer solution is supplied in a manner of 10 kg / hour in terms of resin conversion, and the conditions are set to a barrel temperature of 260°C, a screw speed of 150 rpm, and a vacuum degree of 10 to 40 Torr. The resin devolatilized in the twin-screw extruder is extruded from a strand die, and pelletized after water cooling to obtain a methacrylic resin composition F. The shear rate in the devolatilization device is calculated based on the device shape and operating conditions, and it is 80 s -1 .

[0621] The composition of the methacrylic resin composition F was confirmed to contain 80.9 mass %, 7.0 mass % and 12.1 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 136,000, Mw / Mn was 2.35, Mz / Mw was 1.81, and the glass transition temperature was 134°C.

[0622] [Comparative Manufacturing Example 2]

[0623] The same procedure as in Production Example 2 was carried out except that commercial products were used as phMI and chMI without purification to prepare 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy mixed solution, thereby obtaining a methacrylic resin composition G. The shear rate in the devolatilizer was calculated based on the device shape and operating conditions and was 5.3 s -1 .

[0624] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 220 mass ppm of phMI and 1070 mass ppm of chMI were contained.

[0625] The composition of the obtained granular polymer was confirmed, and the structural units derived from each monomer were 80.9 mass %, 7.1 mass %, and 12.1 mass %, respectively. The weight average molecular weight Mw was 142,000, Mw / Mn was 2.32, Mz / Mw was 1.75, and the glass transition temperature was 134°C.

[0626] [Comparative Manufacturing Example 3]

[0627] As phMI and chMI, commercial products were used without purification. 38.6 kg of phMI, 65.7 kg of chMI, 450.0 kg of mXy, 445.7 kg of MMA and 0.413 kg of n-octyl mercaptan as a chain transfer agent were weighed and put into a 1.25 m3 / 3 liter container equipped with a jacketed temperature control device and a stirring blade. 3reactor and stirred to obtain a monomer mixed solution.

[0628] The liquid content in the reactor was bubbling with nitrogen at a rate of 30 L / min for 1 hour to remove dissolved oxygen.

[0629] Thereafter, steam was blown into the jacket to raise the temperature of the solution in the reactor to 125° C., and a polymerization initiator solution of 0.23 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 2.77 kg of mXy was added at a rate of 0.5 kg / hour while stirring at 50 rpm to start polymerization. The addition was stopped 6 hours after the start of the polymerization.

[0630] During the polymerization, the temperature of the solution in the reactor was controlled at 125±2° C. by temperature regulation using a jacket.

[0631] After 8 hours had passed from the start of the polymerization, a polymerization solution containing a methacrylic resin having a ring structure in its main chain was obtained.

[0632] The amount of N-substituted maleimide contained in the obtained polymerization solution was evaluated, and as a result, 1340 mass ppm of phMI and 4390 mass ppm of chMI were contained.

[0633] To this polymerization solution, 0.1 mass % of Irganox 1010 and 0.05 mass % of Irgafos 168 were added under stirring based on 100 mass % of the polymer contained in the solution.

[0634] The polymerization solution containing the antioxidant was filtered by passing it through a filter having a filtration accuracy of 2 μm and composed of metal fibers made of SUS316L.

[0635] The polymerization solution to which the antioxidant was added was supplied to a concentrating device consisting of a tubular heat exchanger and a vaporizer which had been preheated to 170°C to increase the concentration of the polymer contained in the solution to 70% by mass. The obtained polymerization solution was then supplied to a heat transfer area of ​​0.2 m 2 The devolatilization is carried out using a thin film evaporator with a rotating part.

[0636] At this time, the temperature in the device was 280°C, the supply amount was 30 L / hr, the rotation speed was 400 rpm, and the vacuum degree was 30 Torr. The polymer after devolatilization was pressurized by a gear pump, extruded from a strand die, water-cooled, and pelletized to obtain a methacrylic resin composition H. The shear rate in the thin film evaporator with a rotating part was calculated based on the device shape and operating conditions, and it was 3200 s -1 .

[0637] The composition of the obtained granular polymer was confirmed, and the structural units derived from each monomer were 81.0 mass %, 7.2 mass %, and 11.8 mass %, respectively. In addition, the weight average molecular weight Mw was 136,000, Mw / Mn was 2.21, Mz / Mw was 1.71, and the glass transition temperature was 134°C.

[0638] [Comparative Manufacturing Example 4]

[0639] A methacrylic resin composition I was obtained in the same manner as in Production Example 2 except that the amounts of the monomers in the solution prepared in the reactor were 41.3 kg of phMI, 41.3 kg of chMI, and 357.5 kg of MMA.

[0640] The composition of the methacrylic resin composition I was confirmed to contain 84.1 mass %, 8.0 mass % and 7.9 mass % of structural units derived from each monomer of MMA, phMI and chMI, respectively. The weight average molecular weight Mw was 145,000, Mw / Mn was 2.31, Mz / Mw was 1.77, and the glass transition temperature was 130°C.

[0641] [Comparative Manufacturing Example 5]

[0642] By imidizing polymethyl methacrylate with monomethylamine using a co-rotating twin-screw extruder, a methacrylic resin composition J having a glutarimide-based structural unit was obtained.

[0643] Specifically, a co-rotating twin-shaft extruder with a screw diameter of 40 mm was used, the extruder barrel temperature was set to 270°C, the screw speed was set to 150 rpm, and a polymethyl methacrylate with a weight average molecular weight Mw of 108,000 was supplied at 20 kg / h through a hopper, while nitrogen was circulated into the extruder at a flow rate of 200 mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by mass of monomethylamine was injected from the nozzle relative to 100 parts by mass of the raw resin to carry out the imidization reaction. A reverse flight was placed at the end of the reaction zone (near the vent port) to fill the resin. The pressure of the vent port was reduced to 50 Torr to remove the by-products and excess methylamine after the reaction. The resin coming out of the die head disposed at the outlet of the extruder in a stranded manner was cooled in a water tank and granulated using a granulator to obtain an imide resin.

[0644] Next, a co-rotating twin-shaft extruder with a screw diameter of 40 mm was used, the extruder barrel temperature was set to 250°C, the screw speed was set to 150 rpm, and the obtained imide resin was supplied at 20 kg / hr. After the resin was melted and filled by the kneading block, a mixed solution of dimethyl carbonate and triethylamine was injected from the nozzle as an esterifying agent to reduce the carboxylic acid groups in the resin. Relative to 100 parts by mass of the imide resin, dimethyl carbonate was set to 3.2 parts by mass, and triethylamine was set to 0.8 parts by mass. A reverse thread was placed at the end of the reaction zone to fill the resin. The pressure of the vent port was reduced to 50 Torr to remove the by-products and excess dimethyl carbonate after the reaction. The resin that came out in a stranded manner from the die head arranged at the exit of the extruder was cooled in a water tank and granulated by a granulator to obtain a methacrylic resin composition J having a glutarimide structure.

[0645] The imidization rate of this resin composition was 3.3%, and the content of glutarimide structural units was 5.2% by mass. The shear rate in the twin-screw extruder was calculated based on the device shape and operating conditions, and it was about 80 s -1 .

[0646] The weight average molecular weight Mw was 96,000, Mw / Mn was 1.82, Mz / Mw was 1.48, and the glass transition temperature was 122°C.

[0647] [Examples 1 to 5, Comparative Examples 1 to 5]

[0648] Using the methacrylic resin compositions A to J obtained in the Production Examples and Comparative Production Examples, resin prisms were injection molded by the following method, and various properties were measured.

[0649] 〈Molding of resin prism〉

[0650] After drying the methacrylic resin compositions A to J at 100° C. for 4 hours in a forced air circulation dryer, a right angle prism was injection molded using a mold having a right equilateral triangle with a side of 12.7 mm and a height of 12.7 mm (a triangular prism having a shape obtained by cutting a cube with a side of 12.7 mm at a surface including a diagonal line of a pair of opposing surfaces) with a right angle equilateral triangle with a side of 12.7 mm as a base, using an injection molding machine with a clamping force of 50 T, at a cylinder temperature of 270° C., a mold temperature of 110° C., an injection speed of 10 mm / s, a holding pressure of 50 MPa for 10 seconds, and a cooling time of 100 seconds.

[0651] Furthermore, annealing was performed for 3 hours in an oven set at a temperature 25° C. lower than the glass transition temperature of the methacrylic resin composition.

[0652] [Table 1]

[0653]

[0654] The resin prism for a polarization beam splitter of the present invention can obtain a clear image when forming a polarization beam splitter, and thus can contribute to weight reduction of display devices such as head-mounted displays.

Claims

1. A resin prism for a polarization beam splitter, It is characterized in that The average value of the absolute value of the phase difference is less than 10nm. The content of the fluorescent substance was calculated from the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving in chloroform was measured at an excitation wavelength of 436 nm, and the concentration-intensity conversion formula of the ethanol solution of fluorescein was 0.1×10 -9 ~4.0×10 -9 mol / L, The resin prism for polarization beam splitter comprises methacrylic resin, The methacrylic resin includes a methacrylic resin having a structural unit X and a structural unit derived from a methacrylic acid ester monomer, wherein the structural unit X is a structural unit having a ring structure in the main chain, The structural unit X includes at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide-based structural unit, and a lactone ring structural unit.

2. The resin prism for a polarization beam splitter according to claim 1, in, The average value of the absolute value of the phase difference is 8 nm or less.

3. The resin prism for a polarization beam splitter according to claim 1, in, The content of the fluorescent substance was calculated from the fluorescence intensity at a wavelength of 530 nm when a 2.0 mass % solution obtained by dissolving in chloroform was measured at an excitation wavelength of 436 nm. The content of the fluorescent substance was 0.2×10 -9 ~3.5×10 -9 mol / L.

4. The resin prism for a polarization beam splitter according to claim 1, in, The glass transition temperature Tg is greater than 120°C and below 160°C.

5. The resin prism for a polarization beam splitter according to any one of claims 1 to 4, in, The absolute value of the photoelastic coefficient is 3.0×10 -12 Pa -1 the following.

6. The resin prism for a polarization beam splitter according to any one of claims 1 to 4, in, The light transmittance in the thickest part measured with a D65 light source and a 10° field of view using a spectrocolorimeter was such that the ratio T450 / T680 of the transmittance T450 at a wavelength of 450 nm to the transmittance T680 at a wavelength of 680 nm was 0.95 to 1.

03.

7. The resin prism for a polarization beam splitter according to any one of claims 1 to 4, in, The weight average molecular weight Mw as measured by gel permeation chromatography in terms of polymethyl methacrylate is 80,000 to 170,000.

8. The resin prism for a polarization beam splitter according to any one of claims 1 to 4, in, The ratio of the amount of the methanol-insoluble component to 100 mass % of the total amount of the methanol-insoluble component and the methanol-soluble component is 95 mass % or more.

9. The resin prism for a polarization beam splitter according to claim 1, in, The content of the structural unit derived from the methacrylate monomer is 50 to 97% by mass based on 100% by mass of the methacrylic resin.

10. The resin prism for a polarization beam splitter according to claim 1, in, The structural unit X includes a structural unit derived from an N-substituted maleimide monomer.

11. The resin prism for a polarization beam splitter according to claim 10, in, The structural unit derived from the N-substituted maleimide monomer is at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), [Chemical formula 1] In formula (1), R 1 represents any one of an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms, and R 2 and R 3 Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms; and in R 2 or R 3 In the case of an aryl group, R 2 or R 3 As a substituent, R may or may not contain a halogen atom. 1 may be substituted by a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group, [Chemical formula 2] In formula (2), R 4 represents any one of a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, and an alkyl group having 1 to 12 carbon atoms, and R 5 and R 6 Each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

12. The resin prism for a polarization beam splitter according to claim 11, in, The monomer forming the structural unit represented by formula (1) is one or more of N-phenylmaleimide and N-benzylmaleimide, The monomer forming the structural unit represented by formula (2) is one or more of N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide and N-cyclohexylmaleimide.

13. The resin prism for a polarization beam splitter according to claim 12, in, The molar ratio X1 / X2 of the content X1 of the structural unit represented by the formula (1) to the content X2 of the structural unit represented by the formula (2) is greater than 0 and is 15 or less.

14. The resin prism for a polarization beam splitter according to claim 10, in, The content of the structural unit derived from the N-substituted maleimide monomer is in the range of 5 to 40% by mass based on 100% by mass of the methacrylic resin.

15. The resin prism for a polarization beam splitter according to claim 12, in, The structural unit derived from methyl methacrylate accounts for 79 to 83% by mass, the structural unit derived from N-phenylmaleimide accounts for 6 to 8% by mass, and the structural unit derived from N-cyclohexylmaleimide accounts for 11 to 13% by mass.

16. The resin prism for a polarization beam splitter according to claim 1, in, The structural unit X includes a glutarimide-based structural unit.

17. The resin prism for a polarization beam splitter according to claim 16, in, The glutarimide structural unit is a substance represented by the following general formula (3): [Chemical formula 3] In the above general formula (3), R 7 and R 8 are independently a hydrogen atom or a methyl group, R 9 It is any of a hydrogen atom, a methyl group, a butyl group, and a cyclohexyl group.

18. The resin prism for a polarization beam splitter according to claim 16, in, The content of the glutarimide structural unit is in the range of 3 to 70% by mass based on 100% by mass of the methacrylic resin.

19. The resin prism for a polarization beam splitter according to claim 18, in, The structural unit derived from methyl methacrylate accounts for 65 to 90% by mass, the structural unit derived from styrene accounts for 5 to 15% by mass, and the glutarimide-based structural unit accounts for 5 to 20% by mass.

20. The resin prism for a polarization beam splitter according to claim 1, in, The structural unit X includes a lactone ring structural unit.

21. The resin prism for polarization beam splitter according to claim 20, in, The content of the lactone ring structural unit in the methacrylic resin having a lactone ring structural unit in the main chain is 5 to 40% by mass relative to 100% by mass of the methacrylic resin.

Citation Information

Patent Citations

  • Production of impact-resistant acrylic polymer

    JP1984202213A

  • Method of manufacturing for transparent heat resistant resin and use of the same

    JP2001151814A

  • Optical system for display device, head mounted virtual image display unit and portable computer system

    JP2002116409A

  • Copolymer and method for producing the same

    JP2004168882A

  • Lactone ring-containing polymer, and its manufacturing method and application

    JP2005146084A